Fluororesin for binder for electrochemical device, binder for electrochemical device, electrode mixture, electrode, and secondary battery
By using a tensile fluororesin containing tetrafluoroethylene and hexafluoropropylene units as the binder for electrochemical devices, the problems of insufficient strength of the electrode mixture sheet and high cost of using organic solvents in the prior art are solved, and the bonding of the electrode mixture sheet with excellent strength and the electrode active substance with high efficiency is achieved.
Patent Information
- Application Number
- CN202380058202.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, it is difficult to form an electrode mixture tablet with excellent strength, and the process and cost of using an organic solvent in a battery are relatively high.
A stretchable fluororesin containing tetrafluoroethylene and hexafluoropropylene units is used as the binder for electrochemical devices, which can be directly mixed with the electrode active substance to reduce dependence on the organic solvent.
An electrode mixture tablet with excellent strength is realized, which reduces the process and cost of using organic solvents, and increases the adhesion of the electrode active substance.
Smart Images

Figure BDA0005263160970000091 
Figure BDA0005263160970000411 
Figure BDA0005263160970000441
Abstract
Description
Technical Field
[0001] The present disclosure relates to a fluororesin for a binder for an electrochemical device, a binder for an electrochemical device, an electrode mixture, an electrode, and a secondary battery. Background Art
[0002] Secondary batteries such as lithium-ion secondary batteries are used in small and portable electrical / electronic devices such as notebook personal computers, mobile phones, smart phones, tablet computers, and ultra-notebooks due to their high voltage, high energy density, low self-discharge, low memory effect, and ability to be ultra-lightweight. They are also being put into practical use as a power source for driving vehicles or large fixed power sources such as automobiles. For secondary batteries, it is required to further achieve higher energy density and further improve battery characteristics.
[0003] Patent Document 1 describes an energy storage device in which at least one of a cathode and an anode contains a polytetrafluoroethylene mixed binder material.
[0004] Patent Documents 2 and 3 describe the use of an aqueous dispersion of polytetrafluoroethylene as a binder for a battery.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2017-517862
[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-31179
[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 11-343317 Summary of the invention
[0010] Problems to be solved by the invention
[0011] An object of the present disclosure is to provide a fluororesin for a binder for an electrochemical device, which can form an electrode mixture sheet having excellent strength, a binder for an electrochemical device, an electrode mixture, an electrode, and a secondary battery.
[0012] Means for solving problems
[0013] The present disclosure (1) is a fluororesin used for a binder for an electrochemical device, wherein the fluororesin contains a tetrafluoroethylene unit and a hexafluoropropylene unit and is stretchable.
[0014] The present disclosure (2) is a fluororesin for use in a binder for an electrochemical device, wherein the fluororesin contains tetrafluoroethylene units and hexafluoropropylene units, and the amount of the hexafluoropropylene units is 0.03% by mass or less based on all polymerized units.
[0015] The present disclosure (3) is a binder for an electrochemical device, which is a binder for an electrochemical device substantially composed of a fluororesin, wherein the fluororesin contains a tetrafluoroethylene unit and a hexafluoropropylene unit and is stretchable.
[0016] The present disclosure (4) is a binder for an electrochemical device, which is a binder for an electrochemical device substantially composed of a fluororesin, wherein the fluororesin contains a tetrafluoroethylene unit and a hexafluoropropylene unit, and the amount of the hexafluoropropylene unit is 0.03% by mass or less relative to all polymerized units.
[0017] The present disclosure (5) is the binder for an electrochemical device according to the present disclosure (3) or (4), wherein the fluororesin has an endothermic peak temperature of 320° C. or higher.
[0018] The present disclosure (6) is a binder for an electrochemical device in combination with any one of the present disclosures (3) to (5), wherein the amount of the hexafluoropropylene unit is 1.0% by mass or less based on the total polymerized units.
[0019] The present disclosure (7) is a binder for an electrochemical device in combination with any one of the present disclosures (3) to (6), wherein the fluororesin is modified polytetrafluoroethylene.
[0020] The present disclosure (8) is a binder for an electrochemical device in combination with any one of the present disclosures (3) to (7), wherein the fluororesin is a powder.
[0021] The present disclosure (9) is a binder for an electrochemical device in combination with any one of the present disclosures (3) to (8), wherein the extrusion pressure of the fluororesin at a compression ratio of 100 is 50 MPa or less.
[0022] The present disclosure (10) is a binder for an electrochemical device in combination with any one of the present disclosures (3) to (9), which is a binder for a battery.
[0023] The present disclosure (11) is an electrode mixture comprising the fluororesin described in the present disclosure (1) or (2) or a binder for an electrochemical device in any combination with any one of the present disclosures (3) to (10), and an electrode active material.
[0024] The present disclosure (12) is the electrode mixture described in the present disclosure (11), which is a sheet.
[0025] The present disclosure (13) is an electrode comprising the fluororesin described in the present disclosure (1) or (2) or a binder for an electrochemical device in any combination with any one of the present disclosures (3) to (10), an electrode active material, and a current collector.
[0026] The present disclosure (14) is a secondary battery comprising the electrode described in the present disclosure (13).
[0027] Effects of the Invention
[0028] According to the present disclosure, it is possible to provide a fluororesin for a binder for an electrochemical device that can form an electrode mixture sheet having excellent strength, a binder for an electrochemical device, an electrode mixture, an electrode, and a secondary battery. DETAILED DESCRIPTION
[0029] The present disclosure is described in detail below.
[0030] The present disclosure provides a fluororesin (hereinafter also referred to as a first fluororesin) which is a fluororesin used for a binder for an electrochemical device, wherein the fluororesin contains a tetrafluoroethylene (TFE) unit and a hexafluoropropylene (HFP) unit and is stretchable.
[0031] The first fluororesin has the above-mentioned structure, so it can form an electrode mixture sheet with excellent strength. In addition, since it can be directly mixed with the electrode active material, it is not necessary to use an organic solvent, which can reduce the process and cost of using an organic solvent. Furthermore, the first fluororesin has excellent bonding strength with the active material, so the amount used can be reduced.
[0032] The first fluororesin contains TFE units (polymerized units based on TFE) and HFP units (polymerized units based on HFP).
[0033] The content of the HFP unit can be 2.0% by mass or less relative to the total polymerized units. From the perspective of being able to reduce the extrusion pressure and further improve the strength of the electrode mixture sheet, it is preferably 1.0% by mass or less, more preferably 0.50% by mass or less, further preferably 0.30% by mass or less, even more preferably 0.20% by mass or less, even more preferably 0.10% by mass or less, even more preferably 0.08% by mass or less, particularly preferably 0.05% by mass or less, and most preferably 0.03% by mass or less.
[0034] The content of the HFP unit may be 0.0001% by mass or more, or 0.001% by mass or more, based on the total polymerized units.
[0035] In this specification, the HFP unit refers to a part of the molecular structure of the fluororesin and is derived from HFP.
[0036] In the first fluororesin, the content of the TFE unit may be 98.0% by mass or more, preferably 99.0% by mass or more, based on all polymerized units.
[0037] The first fluororesin may be composed of only TFE units and HFP units, or may contain polymerized units based on other modifying monomers other than HFP (other modifying monomer units) together with TFE units and HFP units.
[0038] As the above-mentioned other modifying monomers, there is no particular limitation as long as they are monomers copolymerizable with TFE and HFP, and examples thereof include hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF]; perhalogenated olefins such as chlorotrifluoroethylene; perfluoroolefins; perfluorovinyl ethers: perfluoroallyl ethers; (perfluoroalkyl)ethylene, ethylene, etc. In addition, the above-mentioned other modifying monomers used may be one or more.
[0039] The content of the other modified monomer units is preferably less than 2.0% by mass, more preferably less than 1.0% by mass, and even more preferably 0.1% by mass or less, based on the total polymerized units.
[0040] When the first fluororesin contains the above-mentioned other modified monomer units, the total amount of the HFP units and the above-mentioned other modified monomer units is preferably 2.0% by mass or less, more preferably 1.0% by mass or less, based on all polymerized units.
[0041] The first fluororesin is preferably modified polytetrafluoroethylene (modified PTFE). In this specification, "modified PTFE" refers to PTFE in which the content of polymerized units (modified monomer units) based on modified monomers that can copolymerize with TFE is less than 1.0 mass % relative to all polymerized units. The content of TFE units in the above-mentioned modified PTFE can be more than 99.0 mass %. The above-mentioned modified PTFE can be composed only of TFE units and modified monomer units.
[0042] The content of each polymerized unit can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the type of monomer.
[0043] The first fluororesin is stretchable. In this specification, "stretchable" is determined according to the following criteria.
[0044] The strip obtained by extruding the paste at a compression ratio (RR) of 100 described later was dried at 230°C for 30 minutes to remove the lubricant. The dried strip was cut into appropriate lengths and placed in a furnace heated to 300°C. In the furnace, the strip was stretched at a stretching speed of 1000% / sec to 25 times the strip length before the tensile test. If it did not break during the stretching, it was judged to be stretchable.
[0045] It is also preferred that the first fluororesin does not break during stretching even when stretched at a stretching rate of 100% / sec to 25 times the length of the strip before the tensile test.
[0046] From the perspective of improving the moldability of the extrudate, the extrusion pressure of the first fluororesin at a compression ratio (RR) of 100 is preferably 50.0 MPa or less, more preferably 40.0 MPa or less, further preferably 35.0 MPa or less, even more preferably 30.0 MPa or less, even more preferably 25.0 MPa or less, even more preferably 20.0 MPa or less, even more preferably less than 18.0 MPa, even more preferably less than 17.0 MPa, particularly preferably less than 16.0 MPa, and particularly preferably less than 15.0 MPa.
[0047] In order to form an electrode mixture sheet having higher strength, the extrusion pressure is preferably 5.0 MPa or more, more preferably 10.0 MPa or more, further preferably 12.0 MPa or more, and still more preferably 14.0 MPa or more.
[0048] The extrusion pressure is a value obtained by the following method.
[0049] Mix 50g of PTFE powder and 10.25g of hydrocarbon oil (trade name: Isopar E, manufactured by Exxon Mobil) as an extrusion aid in a polyethylene container for 3 minutes. At room temperature (25±2°C), fill the barrel of the extruder with the above mixture, apply a load of 0.47MPa to the piston inserted into the barrel and hold it for 1 minute. Then, extrude from the hole at a punching speed of 18mm / min. The ratio of the cross-sectional area of the barrel to the cross-sectional area of the hole (compression ratio) is 100. In the second half of the extrusion operation, the value obtained by dividing the load (N) when the pressure reaches a balanced state by the cross-sectional area of the barrel is used as the extrusion pressure (MPa).
[0050] The thermal instability index (TII) of the first fluororesin is preferably less than 40, more preferably 15 or less, further preferably 10 or less, and particularly preferably less than 5, from the viewpoint of further improving heat resistance.
[0051] The thermal instability index is preferably -10 or greater, more preferably 0 or greater.
[0052] The thermal instability index is measured in accordance with ASTM D 4895.
[0053] From the perspective of improving the bonding force and electrode strength, the standard specific gravity (SSG) of the first fluororesin is preferably 2.280 or less, more preferably 2.250 or less, further preferably 2.200 or less, even more preferably 2.180 or less, even more preferably 2.170 or less, particularly preferably 2.160 or less, and particularly preferably 2.150 or less.
[0054] The standard specific gravity is preferably 2.130 or more, more preferably 2.135 or more, and even more preferably 2.140 or more.
[0055] The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.
[0056] The first fluororesin generally has non-melt secondary processability, which means that the melt flow rate cannot be measured at a temperature higher than the melting point according to ASTM D-1238 and D-2116, in other words, it does not easily flow even in the melting temperature range.
[0057] From the perspective of being able to form an electrode mixture sheet with better strength, the endothermic peak temperature of the first fluororesin is preferably 320° C. or higher, more preferably 325° C. or higher, further preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. In addition, the endothermic peak temperature is preferably 350° C. or lower.
[0058] The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by differential scanning calorimetry [DSC] at a heating rate of 10°C / min for a fluororesin that has not been heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is taken as the endothermic peak temperature.
[0059] The first fluororesin may be a PTFE having a core-shell structure. As the PTFE having a core-shell structure, for example, a modified PTFE containing a core of a high molecular weight PTFE and a shell of a lower molecular weight PTFE or a modified PTFE in the particles may be cited. As such a modified PTFE, for example, the PTFE described in Japanese Patent Publication No. 64-8022 may be cited.
[0060] From the viewpoint of being able to form an electrode mixture sheet with higher strength, the number average molecular weight (Mn) of the first fluororesin is preferably 3.0×10 6 More preferably, 3.2×10 6 More preferably, 3.5×10 6More preferably, 3.7×10 6 More than 4.0×10 6 In addition, the number average molecular weight is preferably 7.0×10 6 Less than, more preferably 6.5×10 6 Below, more preferably 6.0×10 6 Less than, and more preferably 5.5×10 6 the following.
[0061] The number average molecular weight is a molecular weight obtained by estimating the heat of crystallization by measuring the temperature drop of a fluororesin melted by a differential scanning calorimeter (DSC) according to the method described in the following document. The measurement was performed 5 times, and the average of the three values excluding the maximum and minimum values was used.
[0062] Literature: Suwa, T.; Takehisa, M.; Machi, S., J.Appl.Polym.Sci.vol.17, pp.3253(1973).
[0063] The first fluororesin preferably contains substantially no moisture. Thus, it is possible to suppress gas generation and degradation of battery characteristics, and to improve electrode strength. In addition, it is possible to widely select the electrode active material to be combined, which is advantageous in the production process. Substantially containing no moisture means that the moisture content relative to the above-mentioned fluororesin is 0.050 mass % or less.
[0064] The water content is preferably 0.040 mass % or less, more preferably 0.020 mass % or less, further preferably 0.010 mass % or less, still more preferably 0.005 mass % or less, particularly preferably 0.002 mass % or less.
[0065] The above-mentioned water content is measured by the following method.
[0066] The mass of the fluororesin was measured before and after heating at 150°C for 2 hours, and the mass was calculated according to the following formula: Three samples were taken, and the mass was calculated for each sample, and the average value was calculated and adopted.
[0067] Water content (mass %) = [(mass of fluororesin before heating (g)) - (mass of fluororesin after heating (g))] / (mass of fluororesin before heating (g)) × 100
[0068] The first fluororesin preferably contains substantially no fluorine-containing compound having a molecular weight of not more than 1000. Substantially containing no fluorine-containing compound means that the amount of the fluorine-containing compound is not more than 25 ppb by mass based on the fluororesin.
[0069] The amount of the fluorine-containing compound is more preferably less than 25 mass ppb, and further preferably less than 10 mass ppb. The lower limit is not particularly limited, and may be an amount less than the detection limit.
[0070] The amount of the fluorine-containing compound having a molecular weight of 1,000 or less is measured by the following method.
[0071] Weigh 1 g of the sample, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The obtained extract is appropriately concentrated by purging with nitrogen, and the fluorine-containing compounds in the concentrated extract are determined by LC / MS / MS. The molecular weight information is selected from the obtained LC / MS spectrum, and it is confirmed that it is consistent with the structural formula of the candidate fluorine-containing compound. Prepare aqueous solutions with more than 5 levels of the standard substance, perform LC / MS analysis on the aqueous solutions with each content, plot the relationship between the content and the area of the region relative to the content, and draw a calibration curve. Using the above calibration curve, the area of the LC / MS chromatogram of the fluorine-containing compound in the extract is converted into the content of the fluorine-containing compound.
[0072] It should be noted that the lower limit of detection in this measurement method is 10 mass ppb.
[0073] Examples of the fluorine-containing compound having a molecular weight of 1000 or less include fluorine-containing compounds having a molecular weight of 1000 g / mol or less and having a hydrophilic group. The molecular weight of the fluorine-containing compound is preferably 800 or less, more preferably 500 or less.
[0074] The polymerized particles obtained by polymerization in the presence of a fluorinated surfactant generally contain a fluorinated surfactant in addition to the fluorinated resin. In the present specification, the fluorinated surfactant is used during polymerization.
[0075] The fluorine-containing compound having a molecular weight of 1,000 or less may be a compound not added during polymerization, for example, a compound produced as a by-product during polymerization.
[0076] It should be noted that the fluorine-containing compound having a molecular weight of 1000 or less, when containing an anionic part and a cationic part, refers to a fluorine-containing compound having an anionic part having a molecular weight of 1000 or less. The fluorine-containing compound having a molecular weight of 1000 or less does not include fluororesins.
[0077] The hydrophilic group may be, for example, -COOM, -SO2M or -SO3M, and examples thereof include -COOM and -SO3M (wherein M is H, a metal atom, NR 1 4. an imidazolium which may be substituted, a pyridinium which may be substituted, or a phosphonium which may be substituted, R 1H or an organic group. ) or other anionic groups.
[0078] As the fluorinated surfactant, a fluorinated surfactant (anionic fluorinated surfactant) having an anionic portion with a molecular weight of 1000 or less may also be used. The “anionic portion” refers to the portion of the fluorinated surfactant other than the cation. For example, in F(CF2) n1 In the case of COOM, it is "F(CF2) n1 COO” part.
[0079] Examples of the anionic fluorinated surfactant include the following general formula (N 0 ):
[0080] X n0 -Rf n0 -Y 0 (N 0 )
[0081] (Where X n0 is H, Cl or and F. Rf n0 It is a chain, branched or cyclic alkylene group having 3 to 20 carbon atoms in which some or all of the H groups are replaced by F. The alkylene group may contain one or more ether bonds, and some of the H groups may be replaced by Cl. 0 is an anionic group).
[0082] Y 0 The anionic group may be -COOM, -SO2M or -SO3M, or may be -COOM or -SO3M.
[0083] M is H, metal atom, NR 1 4. an imidazolium which may be substituted, a pyridinium which may be substituted, or a phosphonium which may be substituted, R 1 is H or an organic group.
[0084] Examples of the metal atom include alkali metals (Group 1) and alkaline earth metals (Group 2), such as Na, K, or Li.
[0085] As R 1 , can be H or C 1-10 The organic group can be H or C 1-4 The organic group can also be H or C 1-4 of alkyl.
[0086] M can be H, metal atom or NR 1 4, can be H, alkali metal (Group 1), alkaline earth metal (Group 2) or NR 14, may also be H, Na, K, Li or NH4.
[0087] The above Rf n0 In the above formula (A), more than 50% of the H can be replaced by fluorine.
[0088] The above-mentioned fluorinated surfactant may be a single type of fluorinated surfactant or a mixture containing two or more types of fluorinated surfactants.
[0089] Examples of the fluorinated surfactant include compounds represented by the following formula: The fluorinated surfactant may be a mixture of these compounds.
[0090] F(CF2)7COOM,
[0091] F(CF2)5COOM,
[0092] H(CF2)6COOM,
[0093] H(CF2)7COOM,
[0094] CF3O(CF2)3OCHFCF2COOM,
[0095] C3F7OCF(CF3)CF2OCF(CF3)COOM,
[0096] CF3CF2CF2OCF(CF3)COOM,
[0097] CF3CF2OCF2CF2OCF2COOM,
[0098] C2F5OCF(CF3)CF2OCF(CF3)COOM,
[0099] CF3OCF(CF3)CF2OCF(CF3)COOM,
[0100] CF2ClCF2CF2OCF(CF3)CF2OCF2COOM,
[0101] CF2ClCF2CF2OCF2CF(CF3)OCF2COOM,
[0102] CF2ClCF(CF3)OCF(CF3)CF2OCF2COOM,
[0103] CF2ClCF(CF3)OCF2CF(CF3)OCF2COOM and
[0104] [Chemistry 1]
[0105]
[0106] (In each formula, M is H, metal atom, NR 1 4. An imidazolium which may have a substituent, a pyridinium which may have a substituent, or a phosphonium which may have a substituent. 1 is H or an organic group. ).
[0107] It is preferred that the first fluororesin contains substantially no fluorine-containing compounds represented by the above formula.
[0108] In the above formulas, M can be H, a metal atom or NR 1 4, can be H, alkali metal (Group 1), alkaline earth metal (Group 2) or NR 1 4, may also be H, Na, K, Li or NH4.
[0109] R 1 Can be H or C 1-10 The organic group can be H or C 1-4 The organic group can also be H or C 1-4 of alkyl.
[0110] When the first fluororesin contains substantially no fluorine-containing compound represented by the above formula, gas generation and degradation of battery characteristics can be further suppressed, and electrode strength can be further improved.
[0111] The phrase "substantially not containing any of the fluorine-containing compounds represented by the above formula" means that the amount of the fluorine-containing compound is 25 ppb by mass or less based on the fluororesin.
[0112] The amount of the fluorine-containing compound is preferably less than 25 ppb by mass, more preferably 10 ppb by mass or less. The lower limit is not particularly limited, and may be an amount less than the detection limit.
[0113] It is also preferred that the first fluororesin does not substantially contain the following general formula:
[0114] [C n-1 F 2n-1 COO - ]M +
[0115] (where n represents an integer from 9 to 14, M + In this way, the generation of gas and the deterioration of battery characteristics can be further suppressed, and the electrode strength can be further improved.
[0116] The cation M in the above formula + The M is the same as the M mentioned above.
[0117] The term “substantially containing no fluorine-containing compound represented by the above formula” means that the amount of the fluorine-containing compound is 25 ppb by mass or less based on the fluororesin.
[0118] The amount of the fluorine-containing compound is preferably less than 25 ppb by mass, more preferably 10 ppb by mass or less. The lower limit is not particularly limited, and may be an amount less than the detection limit.
[0119] The first fluororesin is preferably in the form of a powder, more preferably a fine powder.
[0120] From the perspective of high molecular weight, improved bonding strength and electrode flexibility, the average primary particle size of the first fluororesin is preferably 350 nm or less, more preferably 330 nm or less, further preferably 320 nm or less, still more preferably 300 nm or less, particularly preferably 280 nm or less, and particularly preferably 250 nm or less. In addition, it is preferably 100 nm or more, more preferably 150 nm or more, further preferably 170 nm or more, and particularly preferably 200 nm or more.
[0121] The average primary particle size is measured by the following method.
[0122] The fluororesin aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the orientation diameter using a transmission electron microscope photograph was prepared. The calibration curve was used to determine the number average particle size from the measured transmittance of the projected light at 550 nm of each sample, which was used as the average primary particle size.
[0123] The average secondary particle size of the first fluororesin may be 350 μm or more, preferably 400 μm or more, more preferably 450 μm or more, and is preferably 1000 μm or less, more preferably 900 μm or less, further preferably 800 μm or less, and still more preferably 700 μm or less.
[0124] The average secondary particle size is measured in accordance with JIS K 6891.
[0125] From the perspective of excellent operability, the average aspect ratio of the primary particles of the first fluororesin may be 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, further preferably 1.6 or less, still more preferably 1.5 or less, still more preferably 1.4 or less, particularly preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. In addition, the above average aspect ratio may be 1.0 or more.
[0126] The average aspect ratio is determined by observing fluororesin powder or an aqueous fluororesin dispersion diluted to a solid content concentration of about 1% by mass using a scanning electron microscope (SEM), performing image processing on 200 or more particles randomly selected, and calculating the average ratio of the major axis to the minor axis.
[0127] From the perspective of excellent workability, the apparent density of the first fluororesin is preferably 0.40 g / ml or more, more preferably 0.43 g / ml or more, further preferably 0.45 g / ml or more, still more preferably 0.48 g / ml or more, and particularly preferably 0.50 g / ml or more. The upper limit is not particularly limited, and may be 0.70 g / ml.
[0128] The above apparent density is measured in accordance with JIS K6892.
[0129] The present disclosure also provides a fluororesin (hereinafter also referred to as a second fluororesin) for use in a binder for an electrochemical device, wherein the fluororesin comprises tetrafluoroethylene units and hexafluoropropylene units, and the amount of the hexafluoropropylene units is 0.03 mass % or less based on all polymerized units.
[0130] The second fluororesin has the above-mentioned structure, so it can form an electrode mixture sheet with excellent strength. In addition, since it can be directly mixed with the electrode active material, it is not necessary to use an organic solvent, which can reduce the process and cost of using an organic solvent. Furthermore, the second fluororesin has excellent bonding strength with the active material, so the amount used can be reduced.
[0131] The second fluororesin contains TFE units (polymerized units based on TFE) and HFP units (polymerized units based on HFP), and the amount of the HFP units is 0.03% by mass or less based on all the polymerized units.
[0132] The content of the HFP unit is preferably 0.025 mass % or less, more preferably 0.02 mass % or less, further preferably 0.015 mass % or less, still more preferably 0.010 mass % or less, particularly preferably 0.005 mass % or less, based on all polymerized units.
[0133] The content of the HFP unit may be 0.0001% by mass or more, or 0.001% by mass or more, based on the total polymerized units.
[0134] The configuration of the resin that can be used as the second fluororesin other than the above-mentioned composition is the same as the configuration described for the resin that can be used as the first fluororesin.
[0135] The first fluororesin and the second fluororesin can be produced, for example, by a production method including the step (A) of emulsion polymerizing TFE and HFP (and other modifying monomers as necessary).
[0136] The above-mentioned emulsion polymerization can be carried out in an aqueous medium in the presence of an anionic fluorinated surfactant and a polymerization initiator, for example.
[0137] The emulsion polymerization can be carried out as follows: an aqueous medium, the anionic fluorinated surfactant, a monomer and other additives as needed are added to a polymerization reactor, the contents of the reactor are stirred, the reactor is maintained at a specified polymerization temperature, and then a specified amount of a polymerization initiator is added to initiate the polymerization reaction. After the polymerization reaction starts, monomers, polymerization initiators, chain transfer agents and the surfactants can be added according to the purpose. Surfactants can also be added after the polymerization reaction starts.
[0138] The polymerization initiator is not particularly limited as long as it can generate free radicals within the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it can also be combined with a reducing agent to initiate polymerization in a redox form. The concentration of the polymerization initiator is appropriately determined according to the type of monomer, the molecular weight of the target fluororesin, and the reaction rate.
[0139] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.
[0140] The oil-soluble free radical polymerization initiator may be a known oil-soluble peroxide, and for example, the following peroxides may be cited as representative substances: dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate; peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate; dialkyl peroxides such as di-tert-butyl peroxide; and di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecanoyl) peroxide, di(perfluorobutanoyl) peroxide, di(perfluoropentanoyl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide. peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetrafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecanoyl)peroxide, di(pentachlorotetrafluorodecanoyl)peroxide, di(undecanotridodecanoyl)peroxide and the like di[perfluoro(or fluorochloro)acyl]peroxides; and the like.
[0141] As the water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. It can also contain a reducing agent such as sulfites and sulfites, and its amount can be 0.1 to 20 times that of the peroxide.
[0142] The amount of the water-soluble free radical polymerization initiator added is not particularly limited, and may be added once, sequentially, or continuously at the initial stage of polymerization in an amount that does not significantly reduce the polymerization rate (e.g., a concentration of several ppm relative to water). The upper limit is a range in which the heat of the polymerization reaction can be used to remove heat from the device surface and the reaction temperature can be increased, and a more preferred upper limit is a range in which the heat of the polymerization reaction can be removed from the device surface.
[0143] From the perspective of easily obtaining the above-mentioned physical properties, especially excellent tensile properties, the amount of polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, relative to the aqueous medium. In addition, it is preferably an amount equivalent to 100 ppm or less, and more preferably an amount equivalent to 10 ppm or less.
[0144] For example, when the polymerization is carried out at a low temperature below 30°C, it is preferred to use a redox initiator that combines an oxidant and a reductant as a polymerization initiator. As the oxidant, persulfates, organic peroxides, potassium permanganate, manganese triacetate, ammonium cerium nitrate, bromates, etc. can be mentioned. As the reductant, sulfites, bisulfites, bromates, diimides, oxalic acid, etc. can be mentioned. As persulfates, ammonium persulfate and potassium persulfate can be mentioned. As sulfites, sodium sulfite and ammonium sulfite can be mentioned. In order to increase the decomposition rate of the initiator, it is also preferred to add copper salts and iron salts to the combination of redox initiators. As copper salts, copper (II) sulfate can be mentioned, and as iron salts, iron (II) sulfate can be mentioned.
[0145] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, persulfate, manganese triacetate, cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is dicarboxylic acid or a salt thereof, or diimine.
[0146] More preferably, the oxidizing agent is permanganic acid or a salt thereof, persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.
[0147] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate.
[0148] When a redox initiator is used, either the oxidant or the reductant may be placed in a polymerization vessel in advance, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferred that ammonium oxalate is placed in the polymerization vessel and potassium permanganate is continuously added thereto.
[0149] It should be noted that, in the redox initiator of the present specification, when "potassium permanganate / ammonium oxalate" is described, it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.
[0150] The redox initiator is particularly preferably a combination of an oxidizing agent which is a salt and a reducing agent which is a salt.
[0151] For example, the oxidizing agent as the salt is more preferably at least one selected from the group consisting of persulfate, permanganate, cerium (IV) salt and bromate, further preferably permanganate, and particularly preferably potassium permanganate.
[0152] The reducing agent for the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.
[0153] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite and cerium ammonium nitrate / ammonium oxalate, and further preferably potassium permanganate / oxalic acid.
[0154] When a redox initiator is used, the oxidant and the reducing agent may be added at once at the beginning of the polymerization, the reducing agent may be added at once and the oxidant may be added continuously at the beginning of the polymerization, the oxidant may be added at once and the reducing agent may be added continuously at the beginning of the polymerization, or both the oxidant and the reducing agent may be added continuously.
[0155] Regarding the above-mentioned redox polymerization initiators, when one is added at the initial stage of polymerization and the remaining one is added continuously, it is preferred to slow down the rate of slow addition from the perspective of obtaining a fluororesin with low SSG, and further preferably to stop the polymerization in the middle of the polymerization. The timing for stopping the addition is preferably before 20% by mass to 40% by mass of the total TFE consumed in the polymerization reaction is consumed.
[0156] When a redox initiator is used as a polymerization initiator, the amount of the oxidant added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, further preferably 5 ppm or more, and further preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less, relative to the aqueous medium. The amount of the reducing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, further preferably 5 ppm or more, and further preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less.
[0157] When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100°C or lower, more preferably 95°C or lower, and further preferably 90°C or lower. It is preferably 10°C or higher, more preferably 20°C or higher, and further preferably 30°C or higher.
[0158] As the polymerization initiator, a water-soluble radical polymerization initiator and a redox initiator are preferred from the viewpoint of improving the adhesive force, electrode strength, and flexibility of the electrode.
[0159] The aqueous medium is a reaction medium for polymerization and is a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and a non-fluorinated organic solvent such as alcohol, ether, or ketone and / or a fluorinated organic solvent having a boiling point of 40° C. or less.
[0160] In the emulsion polymerization, a nucleating agent, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposing agent of a polymerization initiator, and the like may be used as necessary.
[0161] From the viewpoint of easily obtaining the above-mentioned various physical properties, the above-mentioned emulsion polymerization is preferably carried out by adding a nucleating agent. The above-mentioned nucleating agent is preferably added before starting the polymerization reaction.
[0162] As the nucleating agent, a known nucleating agent can be used, and for example, at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents is preferred, and a nonionic surfactant is more preferred.
[0163] Examples of the fluorinated polyether include perfluoropolyether (PFPE) acid and salts thereof.
[0164] The above-mentioned perfluoropolyether (PFPE) acid or its salt may have any chain structure in which oxygen atoms in the main chain of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. In addition, two or more fluorocarbon groups may exist in the molecule. A representative structure has a repeating unit represented by the following formula.
[0165] (-CFCF3-CF2-O-) n
[0166] (-CF2-CF2-CF2-O-) n
[0167] (-CF2-CF2-O-) n -(-CF2-O-) m
[0168] (-CF2-CFCF3-O-) n -(-CF2-O-) m
[0169] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed in the document, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have a sulfonic acid, phosphonic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have different groups at each end. For monofunctional PFPE, the other end of the molecule is usually perfluorinated and may also contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least 2 ether oxygens, preferably at least 4 ether oxygens, and more preferably at least 6 ether oxygens. Preferably, at least one of the fluorocarbon groups separated by the ether oxygen, more preferably at least two of such fluorocarbon groups, has 2 or 3 carbon atoms. More preferably, at least 50% of the fluorocarbon groups separated by the ether oxygen have 2 or 3 carbon atoms. In addition, preferably, the PFPE acid or its salt has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure is at least 5. Two or more PFPE acids or salts thereof having an acid group at one or both ends can be used in the production method of the present disclosure. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.
[0170] From the aspect that fluororesin can be further high molecular weighted, can improve the strength of electrode composite sheet, above-mentioned emulsion polymerization is preferably carried out by adding a decomposition agent of free radical scavenger or polymerization initiator. Above-mentioned free radical scavenger or polymerization initiator decomposition agent is preferably added before polymerization after polymerization reaction starts, preferably more than 10 mass % of all TFE consumed in polymerization reaction, preferably more than 20 mass % is polymerized, in addition, preferably less than 50 mass %, preferably less than 40 mass % is polymerized. In the case of pressure relief and re-pressurization described later, preferably add afterwards.
[0171] As the free radical scavenger, a compound that is added to the free radical in the polymerization system or has no reinitiation ability after chain transfer is used. Specifically, a compound having the following functions is used: it is easy to undergo a chain transfer reaction with a primary free radical or a growing free radical, and then generate a stable free radical that does not react with the monomer, or it is easy to undergo an addition reaction with a primary free radical or a growing free radical to generate a stable free radical.
[0172] The activity of a substance generally referred to as a chain transfer agent is characterized by a chain transfer constant and a reinitiation efficiency. Among chain transfer agents, a substance having a reinitiation efficiency of substantially 0% is referred to as a free radical scavenger.
[0173] The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero%. "Substantially zero% reinitiation efficiency" means that the generated radicals make the radical scavenger a stable radical.
[0174] Preferred are compounds having a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) greater than 0.1, and the chain transfer constant (Cs) of the above-mentioned compound is more preferably 0.5 or more, further preferably 1.0 or more, further preferably 5.0 or more, and particularly preferably 10 or more.
[0175] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl 2 ).
[0176] Examples of the aromatic hydroxy compound include unsubstituted phenol, polyphenol, salicylic acid, m-salicylic acid or p-salicylic acid, gallic acid, and naphthol.
[0177] Examples of the unsubstituted phenol include o-nitrophenol, m-nitrophenol, p-nitrophenol, o-aminophenol, m-aminophenol, p-aminophenol, p-nitrosophenol, etc. Examples of the polyphenol include catechol, resorcinol, hydroquinone, pyrogallol, pyrogallol, naphthol resorcinol, etc.
[0178] Examples of the aromatic amines include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, and benzidine.
[0179] Examples of the quinone compound include o-benzoquinone, m-benzoquinone, p-benzoquinone, 1,4-naphthoquinone, and alizarin.
[0180] Examples of the thiocyanate include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN).
[0181] As the radical scavenger, an aromatic hydroxy compound is preferred, an unsubstituted phenol or a polyphenol is more preferred, and hydroquinone is further preferred.
[0182] From the aspect of reducing the standard specific gravity, the amount of the free radical scavenger added is preferably an amount equivalent to 3% to 500% (molar basis) of the polymerization initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).
[0183] As the decomposition agent of the above-mentioned polymerization initiator, any compound capable of decomposing the polymerization initiator used may be used, for example, at least one selected from the group consisting of sulfites, bisulfites, bromates, diimides, diimide salts, oxalic acid, oxalates, copper salts and iron salts is preferred. As sulfites, sodium sulfite and ammonium sulfite can be cited. As copper salts, copper (II) sulfate can be cited, and as iron salts, iron (II) sulfate can be cited.
[0184] From the aspect of reducing the standard specific gravity, the amount of the above-mentioned decomposition agent added is preferably an amount equivalent to 3% to 500% (molar basis) of the initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).
[0185] In the above-mentioned emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined according to the type of monomer used, the molecular weight of the target fluororesin, and the reaction rate. Usually, the polymerization temperature is 5°C to 150°C, preferably 10°C or more, more preferably 30°C or more, and further preferably 50°C or more. In addition, it is more preferably 120°C or less, and further preferably 100°C or less.
[0186] The polymerization pressure is usually 0.05 MPaG to 10 MPaG. From the perspective of further improving the breaking strength, the polymerization pressure is more preferably 0.3 MPaG or more, and more preferably 0.5 MPaG or more. In addition, it is more preferably 5.0 MPaG or less, and more preferably 3.0 MPaG or less.
[0187] In the above-mentioned emulsion polymerization, from the aspect of easily obtaining the above-mentioned various physical properties, it is preferred that the HFP concentration in the gas in the reactor at the start of the polymerization (when the initiator is added) is set to 0.01 mol% to 3.0 mol%. Furthermore, the HFP concentration in the gas in the reactor at the moment when 40% by mass of all TFE consumed in the polymerization reaction is polymerized is preferably greater than 0 mol% and less than 0.2 mol%. The above-mentioned HFP concentration is preferably maintained until the end of the polymerization reaction. HFP can be put in once before the start of the polymerization, or a part can be put in before the start of the polymerization, and added continuously or intermittently after the start of the polymerization. By leaving HFP to the end of the polymerization reaction, the extrusion pressure is reduced despite the high strength of the electrode mixture sheet using the obtained fluororesin.
[0188] In the emulsion polymerization, from the viewpoint of further improving the breaking strength, it is preferred to release the pressure before 5% to 40% by mass of all TFE consumed in the polymerization reaction is polymerized, and then to increase the pressure again by passing only TFE.
[0189] The pressure reduction is preferably performed so that the pressure in the reactor becomes 0.2 MPaG or less, more preferably 0.1 MPaG or less, and further preferably 0.05 MPaG or less. It is also preferably performed so that the pressure becomes 0.0 MPaG or more.
[0190] The above-mentioned depressurization and re-pressurization may be performed multiple times. Depressurization may be performed to a reduced pressure using a vacuum pump.
[0191] The production method may include a step (B) of subjecting the aqueous dispersion to precipitation to obtain a wet powder of the fluororesin. The precipitation may be performed by a known method.
[0192] The manufacturing method may include a step (C) of drying the wet powder. The drying is usually carried out by vacuum, high frequency, hot air or the like while keeping the wet powder in a state where it is not too fluid, preferably in a static state. Friction between powders, especially at high temperatures, usually has an adverse effect on fine powder PTFE. This is because the particles composed of PTFE have the property of simply fibrillating even when subjected to a small shear force, thereby losing the originally stable particle structure.
[0193] From the perspective of reducing the extrusion pressure, the drying temperature is preferably 300°C or less, more preferably 250°C or less, further preferably 230°C or less, still more preferably 210°C or less, still more preferably 190°C or less, and particularly preferably 170°C or less. From the perspective of improving the breaking strength, it is preferably 10°C or more, more preferably 100°C or more, further preferably 150°C or more, further more preferably 170°C or more, further more preferably 190°C or more, and particularly preferably 210°C or more. In order to further improve the strength ratio, it is preferably adjusted appropriately within this temperature range.
[0194] The step (C) is preferably a step of placing the wet powder in a container having an air-permeable bottom and / or side, and performing a heat treatment at a temperature of 150° C. to 300° C. for 2 hours or more. By performing the heat treatment under extremely limited conditions, the fluorinated compound having a molecular weight of 1000 or less can be efficiently removed together with water, and the content of the fluorinated compound and water can be within the above range.
[0195] From the perspective of being able to more efficiently remove moisture and fluorine-containing compounds, the temperature of the heat treatment in step (C) is preferably 160°C or higher, more preferably 180°C or higher, further preferably 200°C or higher, particularly preferably 220°C or higher, and preferably 280°C or lower.
[0196] From the aspect that water and fluorine-containing compounds can be removed more efficiently, the time of the heat treatment in step (C) is preferably 5 hours or more, more preferably 10 hours or more, and further preferably 15 hours or more. The upper limit is not particularly limited, for example, preferably 100 hours, more preferably 50 hours, and further preferably 30 hours.
[0197] From the aspect of being able to remove water and fluorine-containing compounds more efficiently, the wind speed in step (C) is preferably 0.01 m / s or more, more preferably 0.03 m / s or more, further preferably 0.05 m / s or more, and further more preferably 0.1 m / s or more. In addition, from the aspect of suppressing the scattering of powder, it is preferably 50 m / s or less, more preferably 30 m / s or less, and further preferably 10 m / s or less.
[0198] The heat treatment in step (C) can be carried out using an electric furnace or a steam furnace. For example, a parallel flow box-type electric furnace, a ventilated box-type electric furnace, a ventilated conveyor-type electric furnace, a belt-type electric furnace, a radiant conveyor-type electric furnace, a fluidized bed electric furnace, a vacuum electric furnace, a stirring electric furnace, an airflow electric furnace, a hot air circulation electric furnace or a steam furnace corresponding to the above (the electric furnace in the device name of each of the above-mentioned electric furnaces is replaced with a device of a steam furnace) can be used. From the aspect of being able to more efficiently remove moisture and fluorine-containing compounds, a parallel flow box-type electric furnace, a ventilated box-type electric furnace, a ventilated conveyor-type electric furnace, a belt-type electric furnace, a fluidized bed electric furnace, a hot air circulation electric furnace, and a steam furnace corresponding to the above (the electric furnace in the device name of each of the above-mentioned electric furnaces is replaced with a device of a steam furnace) are preferred.
[0199] The heat treatment in step (C) is performed by placing the wet powder in a container having a permeable bottom and / or side. The container having a permeable bottom and / or side can be any container that can withstand the heat treatment temperature, and is preferably made of metal such as stainless steel.
[0200] The container having an air-permeable bottom and / or side surfaces is preferably a tray (pot) having an air-permeable bottom and / or side surfaces, and more preferably a tray (mesh tray) having a mesh bottom and / or side surfaces.
[0201] The mesh is preferably any one of a woven mesh and a perforated mesh.
[0202] The mesh size of the net is preferably 2000 μm or less (10 meshes or more according to the ASTM standard), more preferably 595 μm or less (30 meshes or more), further preferably 297 μm or less (50 meshes or more), still more preferably 177 μm or less (80 meshes or more), particularly preferably 149 μm or less (100 meshes or more), and particularly preferably 74 μm or less (200 meshes or more). In addition, it is preferably 25 μm or more (500 meshes or less).
[0203] When the net-like material is a woven net, examples of the weaving method include plain weave, twill weave, flat lap weave, and diagonal lap weave.
[0204] When the net is a punched net, the opening ratio is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more, and preferably 95% or less.
[0205] In step (C), the amount of the wet powder is preferably 10 g / cm2 from the viewpoint of more efficient removal of water and fluorine-containing compounds. 2 Below, more preferably 8g / cm 2 Below, more preferably 5g / cm 2 Below, particularly preferably 3g / cm 2Below, preferably 0.01 g / cm 2 More preferably, 0.05 g / cm 2 More preferably, 0.1 g / cm 2 above.
[0206] Regarding the moisture content of the wet powder subjected to heat treatment in step (C), from the perspective of being able to more efficiently remove moisture and fluorine-containing compounds, it is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more, relative to the above-mentioned wet powder, and is preferably 150% by mass or less, and more preferably 100% by mass or less.
[0207] The first fluororesin and the second fluororesin are used in a binder for electrochemical devices. In the above-mentioned binder for electrochemical devices, the first fluororesin and the second fluororesin can be used alone, or can be mixed with other materials (such as polymers other than the first fluororesin and the second fluororesin) for use. It is preferred to use the first fluororesin and the second fluororesin substantially alone, and more preferably to use them alone. It should be noted that using the first fluororesin and the second fluororesin substantially alone means using them in a manner such that the amount of the first fluororesin and the second fluororesin in the binder for electrochemical devices reaches the range described below.
[0208] The present disclosure also provides a binder for an electrochemical device (hereinafter also referred to as a first binder), which is a binder for an electrochemical device substantially composed of only a fluororesin, wherein the fluororesin contains a TFE unit and an HFP unit and is stretchable.
[0209] The first binder contains a specific fluororesin, so it can form an electrode mixture sheet with excellent strength. In addition, since it can be directly mixed with the electrode active material, it is not necessary to use an organic solvent, and the process and cost of using an organic solvent can be reduced. In addition, the first binder has excellent bonding strength with the active material, so the amount can be reduced.
[0210] As the fluororesin in the first binder, the same fluororesin as the above-mentioned first fluororesin can be used, and the preferred aspects are also the same.
[0211] The first binder is substantially composed of the fluororesin alone. Thus, the effect of the fluororesin can be significantly exerted. Substantially composed of the fluororesin alone means that the content of the fluororesin is 95.0% by mass or more relative to the binder.
[0212] The content of the fluororesin is preferably 98.0% by mass or more, more preferably 99.0% by mass or more, further preferably 99.5% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more, based on the binder.
[0213] It is also preferable that the first binder consists only of the above-mentioned fluororesin.
[0214] The first binder preferably contains substantially no organic solvent. This can reduce the process and cost of using an organic solvent. Substantially containing no organic solvent means that the organic solvent content relative to the binder is 5% by mass or less.
[0215] The organic solvent content is preferably 3% by mass or less, more preferably 1% by mass or less, further preferably 0.1% by mass or less, still more preferably 0.01% by mass or less, and particularly preferably 0.001% by mass or less.
[0216] The present disclosure also provides a binder for electrochemical devices (hereinafter also referred to as a second binder), which is a binder for electrochemical devices substantially composed only of a fluororesin, wherein the fluororesin contains tetrafluoroethylene units and hexafluoropropylene units, and the amount of the hexafluoropropylene units is less than 0.03 mass % relative to all polymerized units.
[0217] The second binder comprises a specific fluororesin, and thus can form an electrode mixture sheet with excellent strength. In addition, since it can be directly mixed with the electrode active material, it is not necessary to use an organic solvent, and the process and cost of using an organic solvent can be reduced. In addition, the second binder has excellent bonding strength with the active material, and thus can reduce the amount used.
[0218] As the fluororesin in the second binder, the same fluororesin as the above-mentioned second fluororesin can be used, and the preferred aspects are also the same.
[0219] The configuration of the second binder other than the fluororesin is the same as that described for the first binder.
[0220] The first binder and the second binder are preferably in the form of powder.
[0221] The first binder and the second binder are used in electrochemical devices such as batteries and capacitors.
[0222] Examples of the battery include secondary batteries such as lithium ion batteries.
[0223] The capacitor is not particularly limited, but is preferably an electrochemical capacitor. Examples of the electrochemical capacitor include electric double layer capacitors, hybrid capacitors, redox capacitors, and the like. Examples of the hybrid capacitor include sodium ion capacitors, lithium ion capacitors, and magnesium ion capacitors. Among them, electric double layer capacitors are particularly preferred.
[0224] The first binder and the second binder can be suitably used as a binder for batteries, and can be particularly suitably used as a binder for secondary batteries such as lithium ion batteries.
[0225] The first binder and the second binder can be used to produce electrochemical device components, preferably battery components.
[0226] The first binder and the second binder can be particularly suitably used as a binder for electrodes.
[0227] The first binder and the second binder can also be suitably used as a binder in a solid electrolyte layer of a solid secondary battery.
[0228] The present disclosure also provides an electrode mixture, which comprises the above-mentioned first fluororesin or second fluororesin and a first electrochemical device binder or a second electrochemical device binder, and an electrode active material. The sheet strength of the electrode mixture disclosed in the present disclosure is excellent. If the electrode mixture disclosed in the present disclosure is used, an electrode with excellent strength can be obtained. In addition, even if the amount of the binder is small, the electrode active material can be maintained.
[0229] Examples of the electrode active material include positive electrode active materials and negative electrode active materials.
[0230] As the positive electrode active material, there is no particular limitation as long as it can electrochemically encapsulate and release alkali metal ions. For example, it is preferred to contain an alkali metal and at least one transition metal. As specific examples, transition metal composite oxides containing alkali metals, transition metal phosphate compounds containing alkali metals, conductive polymers, etc. can be cited. Among them, as the positive electrode active material, transition metal composite oxides containing alkali metals that can generate high voltages are particularly preferred. As the above-mentioned alkali metal ions, lithium ions, sodium ions, potassium ions, etc. can be cited. In a preferred embodiment, the alkali metal ions can be lithium ions. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.
[0231] Examples of the alkali metal-containing transition metal composite oxide include
[0232] Formula: M a Mn 2-b M 1 b O4
[0233] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0.9≤a; 0≤b≤1.5; M 1 an alkali metal-manganese spinel composite oxide (lithium-manganese spinel composite oxide, etc.) represented by at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge,
[0234] Formula: MNi 1-c M 2 c O2
[0235] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤c≤0.5; M 2 an alkali metal-nickel composite oxide (lithium-nickel composite oxide, etc.) represented by at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, or
[0236] Formula: MCo 1-d M 3 d O2
[0237] (wherein, M is at least one metal selected from the group consisting of Li, Na and K; 0≤d≤0.5; M 3 An alkali metal-cobalt composite oxide (lithium-cobalt composite oxide, etc.) is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge. Among the above, M is preferably a metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li.
[0238] Among them, MCoO2, MMnO2, MNiO2, MMn2O4, MNi 0.8 Co 0.15 Al 0.05 O2, or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., preferably a compound represented by the following general formula (3).
[0239] MNi h Co i Mn j M 5 k O2 (3)
[0240] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 5 is at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge, (h+i+j+k)=1.0, 0≤h≤1.0, 0≤i≤1.0, 0≤j≤1.5, 0≤k≤0.2.)
[0241] Examples of the alkali metal-containing transition metal phosphate compound include the following formula (4):
[0242] M e M 4 f (PO4) g (4)
[0243] (wherein, M is at least one metal selected from the group consisting of Li, Na and K, M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, 0.5≤e≤3, 1≤f≤2, 1≤g≤3. ) The compound represented by. Among the above, M is preferably a metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and further preferably Li. That is, as the above-mentioned alkali metal-containing transition metal phosphate compound, a lithium-containing transition metal phosphate compound is preferred.
[0244] As the transition metal of the above-mentioned lithium-containing transition metal phosphate compound, V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. are preferred. As specific examples, iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, etc.; cobalt phosphates such as LiCoPO4, etc.; substances obtained by replacing part of the transition metal atoms as the main body of these lithium transition metal phosphate compounds with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. As the above-mentioned lithium-containing transition metal phosphate compound, it is preferred to have an olivine structure.
[0245] As other positive electrode active materials, MFePO4, MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2、MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3, etc. In particular, M2MnO3, MNi 0.5 Mn 1.5 The positive electrode active material such as O2 does not collapse the crystal structure when the secondary battery is operated at a voltage exceeding 4.4V or a voltage above 4.6V, which is preferred from this aspect. Therefore, the electrochemical device such as a secondary battery using the positive electrode material containing the positive electrode active material exemplified above is not easy to reduce the residual capacity and change the resistance increase rate even when stored at high temperature, and the battery performance will not deteriorate even when operating at a high voltage, so it is preferred.
[0246] Other positive electrode active materials include M2MnO3 and MM 6O2 (where M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.). A solid solution material, etc.
[0247] The above-mentioned solid solution material is, for example, an alkali metal manganese oxide represented by the general formula Mx[Mn (1-y) M 7 y O z shown. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 is composed of at least one metal element other than M and Mn, and for example, contains one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. In addition, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O2 such a manganese-containing solid solution material based on Li2MnO3 and solid-solved with LiNiO2 and LiCoO2 can provide an alkali metal ion secondary battery with high energy density and is preferred in this regard.
[0248] In addition, if lithium phosphate is included in the positive electrode active material, the continuous charging characteristics are improved, so it is preferred. The use of lithium phosphate is not limited, and it is preferred to use a mixture of the above-mentioned positive electrode active material and lithium phosphate. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and further preferably 0.5% by mass or more with respect to the lower limit of the total of the above-mentioned positive electrode active material and lithium phosphate, and the upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 5% by mass or less.
[0249] As the above-mentioned conductive polymer, a p-doped conductive polymer and an n-doped conductive polymer can be cited. As the conductive polymer, polyacetylene-based, polystyrene-based, heterocyclic polymers, ionic polymers, ladder and network polymers, etc. can be cited.
[0250] In addition, a substance having a different composition from the above-mentioned positive electrode active material can be attached to the surface of the positive electrode active material, and the positive electrode active material thus obtained can be used. As the surface-attached substance, oxides such as alumina, silica, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like can be cited.
[0251] These surface-attached substances can be attached to the surface of the positive electrode active material by, for example, the following methods: dissolving or suspending in a solvent, adding to the positive electrode active material by infiltration and drying; dissolving or suspending the surface-attached substance precursor in a solvent, adding to the positive electrode active material by infiltration, and then reacting it by heating or the like; adding to the positive electrode active material precursor and firing it at the same time; etc. It should be noted that in the case of attaching carbon, a method of attaching carbon in the form of activated carbon and then mechanically attaching it can also be adopted.
[0252] The amount of the surface-attached substance is preferably 0.1 ppm or more, more preferably 1 ppm or more, and further preferably 10 ppm or more, as a lower limit, and preferably 20% or less, more preferably 10% or less, and further preferably 5% or less, relative to the above-mentioned positive electrode active material, as an upper limit. The surface-attached substance can inhibit the oxidation reaction of the electrolyte on the surface of the positive electrode active material and improve the battery life. If the amount of the surface-attached substance is too small, the effect cannot be fully demonstrated; if the amount of the surface-attached substance is too large, it will hinder the entry and exit of lithium ions, so the resistance may sometimes increase.
[0253] The shape of the particles of the positive electrode active material may be a block shape, a polyhedron shape, a sphere shape, an ellipsoidal sphere shape, a plate shape, a needle shape, a column shape, etc. The primary particles may be aggregated to form secondary particles.
[0254] The tap density of the positive electrode active material is preferably 0.5 g / cm 3 More preferably, 0.8 g / cm 3 More preferably, 1.0 g / cm 3 Above. If the tap density of the positive electrode active material is less than the above lower limit, the amount of dispersion medium required when the positive electrode active material layer is formed increases, and the required amount of conductive material and binder increases. Sometimes, the filling rate of the positive electrode active material in the positive electrode active material layer will be limited, and the battery capacity will be limited. By using a composite oxide powder with a high tap density, a high-density positive electrode active material layer can be formed. The larger the tap density is, the better, and there is no particular upper limit. However, if it is too large, the diffusion of lithium ions using the electrolyte in the positive electrode active material layer as a medium becomes rate-limiting, and sometimes the load characteristics are easily reduced. Therefore, the upper limit is preferably 4.0 g / cm 3 Below, more preferably 3.7 g / cm 3 Below, more preferably 3.5 g / cm 3 the following.
[0255] The tap density is calculated as follows: 5 to 10 g of the positive electrode active material powder is placed in a 10 ml glass cylinder and shaken 200 times with a stroke of about 20 mm. The tap density is g / cm 3 Find out.
[0256] The median diameter d50 of the particles of the positive electrode active material (secondary particle diameter when the primary particles agglomerate to form secondary particles) is preferably 0.3 μm or more, more preferably 0.5 μm or more, further preferably 0.8 μm or more, and most preferably 1.0 μm or more. In addition, it is preferably 30 μm or less, more preferably 27 μm or less, further preferably 25 μm or less, and most preferably 22 μm or less. If it is less than the above lower limit, a high tap density product may not be obtained; if it exceeds the upper limit, the diffusion of lithium in the particles takes time, which may cause a decrease in battery performance, or when the positive electrode of the battery is made, that is, the active material and the conductive material, the binder, etc. are made into a slurry using a solvent and applied in a thin film, stripes and other problems may sometimes occur. Here, by mixing two or more of the above-mentioned positive electrode active materials with different median diameters d50, the filling property during the production of the positive electrode can be further improved.
[0257] The median diameter d50 is measured by a known laser diffraction / scattering particle size distribution measuring device. When using LA-920 manufactured by HORIBA as a particle size distribution meter, as a dispersion medium used during measurement, a 0.1 mass % sodium hexametaphosphate aqueous solution is used, and after 5 minutes of ultrasonic dispersion, the measured refractive index is set to 1.24 for measurement.
[0258] In the case where the primary particles are agglomerated to form secondary particles, the average primary particle size of the positive electrode active material is preferably 0.05 μm or more, more preferably 0.1 μm or more, and further preferably 0.2 μm or more, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less, further preferably 3 μm or less, and most preferably 2 μm or less. If the upper limit is exceeded, it is difficult to form spherical secondary particles, which has an adverse effect on the powder filling property, or the specific surface area is greatly reduced, so the possibility of reduced battery performance such as output characteristics is sometimes increased. On the contrary, if it is lower than the lower limit, crystallization is usually not developed, so problems such as poor reversibility of charge and discharge may occur.
[0259] The above average primary particle size is measured by observation using a scanning electron microscope (SEM). Specifically, for any 50 primary particles in a photograph with a magnification of 10,000 times, the longest value of a slice intercepted on a straight line in the horizontal direction by the left and right boundaries of the primary particles is obtained, and the average value is taken to obtain the primary particle size.
[0260] The BET specific surface area of the positive electrode active material is preferably 0.1 m2 / g or more, more preferably 0.2m 2 / g or more, more preferably 0.3m 2 / g or more, and the upper limit is preferably 50m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 If the BET specific surface area is smaller than this range, the battery performance is likely to decrease; if the BET specific surface area is larger than this range, it is difficult to increase the tap density, and sometimes problems may arise in the coating properties when the positive electrode active material layer is formed.
[0261] The above-mentioned BET specific surface area is defined as follows: using a surface area meter (for example, a fully automatic surface area measuring device manufactured by Okura Riken Co., Ltd.), the sample is pre-dried at 150°C for 30 minutes under nitrogen flow, and then a nitrogen-helium mixed gas accurately adjusted to a relative pressure value of 0.3 relative to atmospheric pressure is used to measure the sample by the nitrogen adsorption BET single-point method based on the gas flow method, and the obtained value is used to define the BET specific surface area.
[0262] When the secondary battery disclosed herein is used as a large lithium-ion secondary battery for hybrid vehicles or distributed power sources, high output is required, so the particles of the above-mentioned positive electrode active material are preferably mainly secondary particles. The particles of the above-mentioned positive electrode active material preferably have an average particle size of secondary particles of less than 40 μm, and contain 0.5% to 7.0% by volume of microparticles with an average primary particle size of less than 1 μm. By containing microparticles with an average primary particle size of less than 1 μm, the contact area with the electrolyte becomes larger, which can further accelerate the diffusion of lithium ions between the electrode mixture and the electrolyte, and as a result, the output performance of the battery can be improved.
[0263] As a method for manufacturing positive electrode active materials, a common method for manufacturing inorganic compounds is used. In particular, various methods are considered for making spherical or ellipsoidal active materials, for example, the following methods can be cited: dissolving or crushing the raw material of the transition metal and dispersing it in a solvent such as water, adjusting the pH under stirring, making a spherical precursor and recovering it, drying it as needed, then adding LiOH, Li2CO3, LiNO3 and other Li sources and firing at high temperature to obtain the active material.
[0264] In order to manufacture the positive electrode, the above-mentioned positive electrode active materials can be used alone, or two or more of different compositions can be used together in any combination or ratio. As a preferred combination in this case, LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33O2 and other ternary combinations, LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced by other transition metals, or a combination of LiFePO4 and LiCoO2 or a portion of the Co is replaced by other transition metals, etc.
[0265] From the aspect of high battery capacity, the content of the above-mentioned positive electrode active material is preferably 50% to 99.5% by mass of the positive electrode mixture, and more preferably 80% to 99% by mass. In addition, the content in the positive electrode active material layer is preferably 80% by mass or more, more preferably 82% by mass or more, and particularly preferably 84% by mass or more. In addition, the upper limit is preferably 99% by mass or less, and more preferably 98% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the capacitance is sometimes insufficient. On the contrary, if the content is too high, the strength of the positive electrode is sometimes insufficient.
[0266] The negative electrode active material is not particularly limited, and examples thereof include materials selected from lithium metal, artificial graphite, graphite carbon fiber, resin-fired carbon, pyrolysis vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-fired carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and carbon containing carbonaceous materials such as non-graphitizable carbon, silicon-containing compounds such as silicon and silicon alloys, Li4Ti5O 12 Among them, a substance containing at least a part of a carbonaceous material or a silicon-containing compound can be particularly preferably used.
[0267] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By containing silicon as a constituent element, a high-capacity battery can be produced.
[0268] As the material containing silicon, silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, silicon oxide particles represented by the general formula SiOx (0.5≤x≤1.6), or mixtures thereof are preferred. By using these substances, a negative electrode mixture for a lithium ion secondary battery having higher initial charge and discharge efficiency, high capacity, and excellent cycle characteristics is obtained.
[0269] Silicon oxide in the present disclosure is a general term for amorphous silicon oxides, and silicon oxide before disproportionation is represented by the general formula SiOx (0.5≤x≤1.6). x is preferably 0.8≤x<1.6, and more preferably 0.8≤x<1.3. The silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon and cooling and precipitating the generated silicon monoxide gas.
[0270] Particles having a structure in which silicon particles are dispersed in a silicon-based compound can be obtained, for example, as follows: a method in which silicon particles are mixed with a silicon-based compound and the mixture is fired; or silicon oxide particles before disproportionation represented by the general formula SiOx are heat-treated in an inactive, non-oxidizing atmosphere such as argon at a temperature of 400°C or more, preferably 800°C to 1,100°C, to carry out a disproportionation reaction, thereby obtaining. In particular, the material obtained by the latter method is preferred because the silicon crystallites are uniformly dispersed. The above-mentioned disproportionation reaction can make the size of silicon nanoparticles 1nm to 100nm. It should be noted that the silicon oxide in the particles having a structure in which silicon nanoparticles are dispersed in silicon oxide is preferably silicon dioxide. It should be noted that the silicon nanoparticles (crystals) dispersed in the amorphous silicon oxide can be confirmed by transmission electron microscopy.
[0271] The physical properties of the particles containing silicon can be appropriately selected according to the target composite particles. For example, the average particle size is preferably 0.1 μm to 50 μm, and the lower limit is more preferably 0.2 μm or more, and further preferably 0.5 μm or more. The upper limit is more preferably 30 μm or less, and further preferably 20 μm or less. The above average particle size is represented by the weight average particle size in the particle size distribution measurement based on the laser diffraction method.
[0272] The BET specific surface area is preferably 0.5 m 2 / g~100m 2 / g, more preferably 1m 2 / g~20m 2 / g. If the BET specific surface area is 0.5m 2 / g or more, there is no possibility of reduced adhesion when applied to the electrode and reduced battery characteristics. 2 / g or less, the proportion of silicon dioxide on the particle surface becomes large, and there is a possibility that the battery capacity will not decrease when used as a negative electrode material for a lithium ion secondary battery.
[0273] By coating the silicon-containing particles with carbon to impart conductivity, it is observed that the battery characteristics are improved. As methods for imparting conductivity, there can be cited a method of mixing the silicon-containing particles with conductive particles such as graphite, a method of coating the surface of the silicon-containing particles with a carbon coating, and a method of combining the two, preferably a method of coating with a carbon coating, and more preferably a method of performing chemical vapor deposition (CVD).
[0274] In order to increase the capacity of the obtained electrode mixture, the content of the above-mentioned negative electrode active material is preferably more than 40 mass %, more preferably more than 50 mass %, and particularly preferably more than 60 mass % in the electrode mixture. In addition, the upper limit is preferably below 99 mass %, more preferably below 98 mass %.
[0275] The electrode mixture disclosed in the present invention preferably further comprises a conductive aid.
[0276] As the above-mentioned conductive auxiliary agent, any known conductive material can be used. As specific examples, metal materials such as copper and nickel, graphite (graphite) such as natural graphite and artificial graphite, carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, needle coke, carbon nanotubes, fullerene, carbon materials such as amorphous carbon such as VGCF, etc. can be cited. It should be noted that they can be used alone or in any combination and ratio. Two or more kinds can be used together.
[0277] The conductive aid is used in an amount of 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more, and usually 50% by mass or less, preferably 30% by mass or less, and more preferably 15% by mass or less in the electrode mixture. If the content is lower than this range, the conductivity is sometimes insufficient. On the contrary, if the content is higher than this range, the battery capacity is sometimes reduced.
[0278] The electrode mixture of the present disclosure may further include a thermoplastic resin. Examples of the thermoplastic resin include polyvinylidene fluoride, polypropylene, polyethylene, polystyrene, polyethylene terephthalate, polyethylene oxide, etc. One type may be used alone, or two or more types may be used in any combination and ratio.
[0279] Thermoplastic resin is generally more than 0.01 mass %, preferably more than 0.05 mass %, more preferably more than 0.10 mass %, in addition, generally below 3.0 mass %, preferably below 2.5 mass %, more preferably below 2.0 mass %.By adding thermoplastic resin, the mechanical strength of electrode can be improved.In addition, if it exceeds this scope, the ratio of electrode active material in electrode mixture is reduced, and sometimes the problem of the capacity reduction of battery or the problem of resistance increase between active material can be produced.
[0280] In the electrode mixture disclosed in the present invention, the content of the binder can be 0.1% by mass or more, preferably 0.2% by mass or more, more preferably 0.5% by mass or more relative to the above-mentioned electrode mixture, and can be 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less, and more preferably 10% by mass or less, particularly preferably 5% by mass or less, and most preferably 3% by mass or less. If the proportion of the binder is too low, the electrode mixture active material can sometimes not be fully retained, and the mechanical strength of the electrode mixture sheet is insufficient, which can deteriorate the battery performance such as cycle characteristics. On the other hand, if the proportion of the binder is too high, it sometimes leads to a reduction in battery capacity and conductivity. The binding force of the binder disclosed in the present invention is excellent, so even if the content is small, the electrode active material can be fully retained.
[0281] In the electrode mixture disclosed in the present invention, the binder component is preferably substantially composed of the above-mentioned fluororesin only, and more preferably composed of the above-mentioned fluororesin only. The binder component is substantially composed of the above-mentioned fluororesin only means that the content of the above-mentioned fluororesin in the binder component constituting the electrode mixture is 95.0% by mass or more relative to the above-mentioned binder component. The content of the above-mentioned fluororesin is preferably 98.0% by mass or more, more preferably 99.0% by mass or more, further preferably 99.5% by mass or more, particularly preferably 99.9% by mass or more, and most preferably 99.95% by mass or more relative to the above-mentioned binder component.
[0282] The electrode mixture disclosed in the present invention is preferably in the form of a tablet.
[0283] The electrode mixture disclosed in the present invention can be suitably used as an electrode mixture for secondary batteries. In particular, the electrode mixture disclosed in the present invention is suitable for lithium-ion secondary batteries. When the electrode mixture disclosed in the present invention is used in a secondary battery, it is usually used in a sheet form.
[0284] The method for producing the electrode mixture sheet is not limited, and an example of a specific production method is shown below.
[0285] The following manufacturing method is preferred, characterized in that it comprises:
[0286] Step (a): a step of mixing the powder components and the binder to form an electrode mixture; and
[0287] Step (b): a step of rolling or extruding the electrode mixture to form a sheet,
[0288] The mixing in step (a) comprises:
[0289] (a1) a step of homogenizing the powder components and the binder to form a powder;
[0290] (a2) A step of mixing the powdery raw material mixture obtained in step (a1) to prepare an electrode mixture.
[0291] For example, PTFE has two transition temperatures at about 19°C and about 30°C. At less than 19°C, PTFE can be easily mixed while maintaining its shape. However, if it exceeds 19°C, the structure of the PTFE particles becomes loose and becomes more sensitive to mechanical shear. At a temperature exceeding 30°C, a higher degree of fibrillation occurs.
[0292] Therefore, the homogenization of (a1) is preferably carried out at a temperature of 19°C or lower, preferably 0°C to 19°C.
[0293] That is, in such (a1), it is preferred to perform mixing and homogenization while suppressing fibrillation.
[0294] The mixing in the next step (a2) is preferably performed at a temperature of 30° C. or higher to promote fibrillation.
[0295] The step (a2) is preferably performed at a temperature of 30°C to 150°C, more preferably 35°C to 120°C, and still more preferably 40°C to 80°C.
[0296] In one embodiment, the calendering or extrusion in the step (b) is performed at a temperature between 30°C and 150°C, preferably between 35°C and 120°C, and more preferably between 40°C and 100°C.
[0297] The mixing in the step (a) is preferably performed while applying a shearing force.
[0298] Specific examples of the mixing method include a W-type mixer, a V-type mixer, a drum mixer, a ribbon mixer, a conical screw mixer, a single-screw kneader, a twin-screw kneader, a mill, a stirring mixer, a planetary mixer, a Henschel mixer, a high-speed mixer, and the like.
[0299] The mixing conditions can be set by appropriately setting the rotating speed and mixing time. For example, the rotating speed is preferably below 15000rpm. It is preferably above 10rpm, more preferably above 1000rpm, and more preferably above 3000rpm. In addition, it is preferably below 12000rpm, more preferably below 11000rpm, and more preferably within the scope of 10000rpm. If it is lower than the above-mentioned range, mixing takes time and productivity is affected. In addition, if it exceeds the above-mentioned range, fibrillation is excessively carried out, and it is possible to become an electrode mixture sheet with poor strength.
[0300] In the step (a1), it is preferred to perform the step with a shearing force weaker than that in the step (a2).
[0301] In the step (a2), the raw material composition preferably does not contain a liquid solvent, but a small amount of lubricant may be used. That is, a lubricant may be added to the powdered raw material mixture obtained in the step (a1) to prepare a paste.
[0302] The lubricant is not particularly limited, and examples thereof include water, ether compounds, alcohols, ionic liquids, carbonates, aliphatic hydrocarbons (low polar solvents such as heptane and xylene), isoparaffinic hydrocarbon compounds and petroleum fractions (gasoline (C4-C10), naphtha (C4-C11), kerosene / paraffins (C10-C16) and mixtures thereof).
[0303] The water content of the lubricant is preferably 1000 ppm or less.
[0304] The water content is preferably 1000 ppm or less in terms of reducing the degradation of the electrochemical device. The water content is more preferably 500 ppm or less.
[0305] When the above lubricants are used, low-polarity solvents such as heptane and xylene, and ionic liquids are particularly preferred.
[0306] When the lubricant is used, the amount thereof may be 5.0 to 35.0 parts by weight, preferably 10.0 to 30.0 parts by weight, and more preferably 15.0 to 25.0 parts by weight, based on the total weight of the composition to be used in step (a1).
[0307] The above-mentioned raw material composition preferably does not contain a liquid medium in substance. The existing electrode mixture forming method usually uses a solvent that dissolves the binder to prepare a slurry in which the powder as the electrode mixture component is dispersed, and the electrode mixture sheet is prepared by coating / drying the slurry. In this case, a solvent that dissolves the binder is used. However, the solvent that can dissolve the binder resin commonly used in the past is limited to specific solvents such as butyl butyrate. They react with the solid electrolyte and deteriorate the solid electrolyte, which sometimes becomes the reason for the reduction of battery performance. In addition, in the case of low-polarity solvents such as heptane, the dissolved binder resin is very limited, and sometimes the flash point is low and the operation becomes complicated.
[0308] By using a powdery binder with less water content instead of a solvent when forming an electrode mixture sheet, a battery with less degradation of a solid electrolyte can be manufactured. Furthermore, in the above-mentioned manufacturing method, an electrode mixture sheet containing a binder having a fine fiber structure can be manufactured, and by not preparing a slurry, the burden of the manufacturing process can be reduced.
[0309] Step (b) is calendering or extrusion. Calendering and extrusion can be performed by known methods. Thus, the electrode mixture can be formed into the shape of an electrode mixture sheet.
[0310] The step (b) preferably includes: (b1) forming the electrode mixture obtained in the step (a) into a block; and (b2) forming the block of the electrode mixture by calendering or extrusion.
[0311] Molding into a block shape means forming the electrode mixture into one block.
[0312] Specific examples of the method for forming the block include extrusion molding, press molding, and the like.
[0313] In addition, the so-called "block-shaped" is not a particularly specific shape, as long as it is in a block-shaped state, including rod-shaped, sheet-shaped, spherical, cubic and other forms. The size of the block is preferably such that the diameter of the cross section or the smallest side is 10000 μm or more, and more preferably 20000 μm or more.
[0314] As a specific method of the calendering or extrusion molding in the step (b2), there can be mentioned a method of calendering the electrode mixture using a roll press, a calender roll machine or the like.
[0315] The step (b) is preferably performed at 30° C. to 150° C. As described above, PTFE has a glass transition temperature of about 30° C. and is therefore easily fibrillated at 30° C. or higher. Therefore, the step (b) is preferably performed at such a temperature.
[0316] Furthermore, since shearing force is applied during calendering or extrusion, PTFE is fibrillated and molded.
[0317] After step (b), it is also preferred to have a step (c) of applying a greater load to the obtained calendered sheet to calender it into a thinner sheet. It is also preferred to repeat step (c). In this way, instead of thinning the calendered sheet once, the calendering is performed little by little in stages, thereby making the pliability better.
[0318] The number of times of performing step (c) is preferably 2 to 10 times, and more preferably 3 to 9 times.
[0319] As a specific calendering method, for example, there is a method in which two or more rolls are rotated and a calendered sheet is passed between the rolls to thereby process the sheet into a thinner sheet.
[0320] In addition, from the perspective of adjusting the sheet strength, it is also preferred to have a step (d) after the step (b) or step (c): the rolled sheet is roughly crushed and then re-molded into a block shape, and rolled into a sheet shape. It is also preferred to repeat the step (d). The number of times of the step (d) is preferably 1 to 12 times, and more preferably 2 to 11 times.
[0321] In step (d), as a specific method for roughly crushing the calendered sheet and forming it into a block, there can be cited a method of folding the calendered sheet, a method of forming it into a rod or a film sheet, a method of forming it into a chip, etc. In the present disclosure, "roughly crushing" means changing the form of the calendered sheet obtained in step (b) or step (c) into another form in order to calender it into a sheet in the next step, and also includes the case of simply folding the calendered sheet.
[0322] In addition, the step (c) may be performed after the step (d), or the steps may be performed repeatedly.
[0323] Furthermore, uniaxial stretching or biaxial stretching may be performed in the steps (a) or (b), (c), and (d).
[0324] In addition, the sheet strength can also be adjusted by adjusting the degree of coarse pulverization in step (d).
[0325] In the above-mentioned steps (b), (c) or (d), the calendering rate is preferably more than 10%, more preferably more than 20%, and is preferably less than 80%, more preferably less than 65%, and more preferably less than 50%. If it is less than the above-mentioned range, it will take time as the number of calendering increases, which will affect productivity. In addition, if it exceeds the above-mentioned range, fibrillation is excessively carried out, and it is possible to become an electrode mixture sheet with poor strength and flexibility.
[0326] It should be noted that the rolling rate mentioned here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before the rolling process. The sample before rolling can be a block-shaped raw material composition or a sheet-shaped raw material composition. The thickness of the sample refers to the thickness in the direction of applying the load during rolling.
[0327] The steps (c) to (d) are preferably performed at 30°C or higher, more preferably 60°C or higher, and preferably 150°C or lower.
[0328] The electrode mixture sheet can be used as an electrode mixture sheet for a secondary battery, and can be made into either a negative electrode or a positive electrode. The electrode mixture sheet is particularly suitable for a lithium ion secondary battery.
[0329] The present disclosure also provides an electrode comprising the first fluororesin or the second fluororesin or the first electrochemical device binder or the second electrochemical device binder, an electrode active material, and a current collector. The electrode of the present disclosure has excellent strength.
[0330] The electrode of the present disclosure may include the electrode mixture of the present disclosure (preferably an electrode mixture sheet) and a current collector.
[0331] The electrode disclosed herein may be a positive electrode or a negative electrode.
[0332] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. Examples of the material of the positive electrode current collector include: metals such as aluminum, titanium, tantalum, stainless steel, nickel, or metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.
[0333] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal plate mesh, stamping metal, foamed metal, etc. can be cited, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be cited. Among these, metal foil is preferred. It should be noted that the metal foil can be suitably formed into a mesh. The thickness of the metal foil is arbitrary, usually more than 1 μm, preferably more than 3 μm, more preferably more than 5 μm, and usually less than 1 mm, preferably less than 100 μm, more preferably less than 50 μm. If the metal foil is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the metal foil is thicker than this range, the handleability is sometimes impaired.
[0334] In addition, from the perspective of reducing the electrical contact resistance between the current collector and the positive electrode active material layer, it is also preferred that a conductive additive be coated on the surface of the current collector. Examples of the conductive additive include carbon or noble metals such as gold, platinum, and silver.
[0335] The ratio of the thickness of the current collector to the positive electrode mixture is not particularly limited, and the value of (the thickness of the positive electrode mixture on one side before the electrolyte is injected) / (the thickness of the current collector) is preferably less than 20, more preferably less than 15, and most preferably less than 10. In addition, it is preferably more than 0.5, more preferably more than 0.8, and most preferably more than 1. If it exceeds this range, the current collector sometimes generates heat caused by Joule heat during high current density charging and discharging. If it is less than this range, the volume ratio of the current collector to the positive electrode active material increases, and the capacity of the battery sometimes decreases.
[0336] The positive electrode may be produced by a conventional method, for example, a method in which the electrode mixture sheet and the current collector are laminated with a binder and vacuum dried.
[0337] The density of the positive electrode mixture sheet is preferably 3.00 g / cm 3 More preferably, 3.10 g / cm 3 More preferably, 3.20 g / cm 3 More than 3.80 g / cm 3 Below, more preferably 3.75g / cm 3 Below, more preferably 3.70 g / cm 3 If the range is exceeded, the permeability of the electrolyte to the collector / active material interface is reduced, and the charge-discharge characteristics at high current density are reduced, and sometimes high output cannot be obtained. In addition, if it is less than this range, the conductivity between the active materials is reduced, and sometimes the battery resistance increases and high output cannot be obtained.
[0338] From the perspective of high output and improved stability at high temperatures, the area of the positive electrode mixture sheet is preferably larger than the outer surface area of the battery case. Specifically, relative to the surface area of the outer packaging of the secondary battery, the sum of the electrode mixture areas of the positive electrode is preferably 15 times or more in terms of area ratio, and more preferably 40 times or more. Regarding the outer surface area of the battery case, in the case of a square shape with a bottom, it refers to the total area calculated by the length, width and thickness dimensions of the shell part filled with the power generation element except the protruding portion of the terminal. In the case of a cylindrical shape with a bottom, it refers to the geometric surface area of the shell part filled with the power generation element except the protruding portion of the terminal. The sum of the electrode mixture areas of the positive electrode refers to the geometric surface area of the positive electrode mixture layer facing the mixture layer containing the negative electrode active material. In a structure where a positive electrode mixture layer is formed on both sides by a collector foil, it refers to the sum of the areas calculated for each face.
[0339] The thickness of the positive electrode is not particularly limited. From the perspective of high capacity and high output, the thickness of the composite layer after deducting the thickness of the metal foil of the collector is preferably 10 μm or more, more preferably 20 μm or more, relative to a single side of the collector as the lower limit. In addition, it is preferably 500 μm or less, more preferably 450 μm or less.
[0340] In addition, a positive electrode having a substance having a different composition attached to the surface of the positive electrode may also be used. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate; carbon; and the like.
[0341] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials are preferred, and copper, nickel, or alloys thereof are particularly preferred.
[0342] As the shape of the current collector, in the case of metal materials, metal foil, metal cylinder, metal coil, metal plate, metal plate mesh, stamping metal, foamed metal, etc. can be cited, and in the case of carbon materials, carbon plate, carbon film, carbon cylinder, etc. can be cited. Among these, metal foil is preferred. It should be noted that the metal foil can be suitably formed into a mesh. The thickness of the metal foil is arbitrary, usually more than 1 μm, preferably more than 3 μm, more preferably more than 5 μm, and usually less than 1 mm, preferably less than 100 μm, more preferably less than 50 μm. If the metal foil is thinner than this range, the strength required as a current collector is sometimes insufficient. On the contrary, if the metal foil is thicker than this range, the handleability is sometimes impaired.
[0343] The negative electrode may be produced by a conventional method, for example, a method in which the electrode mixture sheet and the current collector are laminated with a binder and then vacuum dried.
[0344] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More than, preferably 2.0 g / cm 3 Below, more preferably 1.9 g / cm 3 Below, more preferably 1.8 g / cm 3 If the range is exceeded, the permeability of the electrolyte to the collector / active material interface is reduced, and the charge-discharge characteristics at high current density are reduced, and sometimes high output cannot be obtained. In addition, if it is less than this range, the conductivity between the active materials is reduced, and sometimes the battery resistance increases and high output cannot be obtained.
[0345] The thickness of the negative electrode is not particularly limited. From the perspective of high capacity and high output, the thickness of the composite layer after deducting the thickness of the metal foil of the collector is preferably 10 μm or more, more preferably 20 μm or more, relative to a single side of the collector as the lower limit. In addition, it is preferably 500 μm or less, more preferably 450 μm or less.
[0346] The present disclosure also provides a secondary battery including the electrode of the present disclosure.
[0347] The secondary battery disclosed herein may be a secondary battery using an electrolyte solution or a solid-state secondary battery.
[0348] The secondary battery using the above-mentioned electrolyte solution can use the electrolyte solution, separator, etc. used for a well-known secondary battery. These will be described in detail below.
[0349] As the electrolyte solution, a non-aqueous electrolyte solution is preferably used. As the non-aqueous electrolyte solution, a solution prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving the electrolyte salt can be used.
[0350] There are no particular limitations on the organic solvent used to dissolve the electrolyte salt, and known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate can be used; and one or more of fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.
[0351] As electrolyte salts, for example, LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, etc. can be mentioned. From the perspective of good cycle characteristics, LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2 or a combination thereof is particularly preferred.
[0352] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.
[0353] The secondary battery using the above electrolyte preferably also has a diaphragm. There is no particular limitation on the material and shape of the diaphragm as long as the electrolyte is stable and has excellent liquid retention, and a known diaphragm can be used. Among them, it is preferred to use a porous sheet or non-woven fabric-like material formed of a material stable to the above electrolyte, using resin, glass fiber, inorganic material, etc., and having excellent liquid retention.
[0354] As materials for resin and glass fiber separators, for example, polyolefins such as polyethylene and polypropylene, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, glass filters, etc. can be used. These materials such as polypropylene / polyethylene two-layer membranes and polypropylene / polyethylene / polypropylene three-layer membranes can be used alone or in any combination and ratio. Among them, from the perspective of good permeability of the electrolyte and good shutdown effect, the above-mentioned separator is preferably a porous sheet or non-woven fabric made of polyolefins such as polyethylene and polypropylene.
[0355] The thickness of the separator is arbitrary, usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is too thin compared to the above range, the insulation and mechanical strength are sometimes reduced. In addition, if it is too thick compared to the above range, the battery performance such as rate characteristics is sometimes reduced, and the energy density of the electrolyte battery as a whole is sometimes reduced.
[0356] In addition, when a porous material such as a porous sheet or nonwoven fabric is used as a diaphragm, the porosity of the diaphragm is arbitrary, usually 20% or more, preferably 35% or more, more preferably 45% or more, and usually 90% or less, preferably 85% or less, more preferably 75% or less. If the porosity is too small compared to the above range, there is a tendency for the membrane resistance to increase and the rate characteristics to deteriorate. In addition, if it is too large compared to the above range, there is a tendency for the mechanical strength of the diaphragm to decrease and the insulation to decrease.
[0357] In addition, the average pore size of the diaphragm is also arbitrary, usually 0.5 μm or less, preferably 0.2 μm or less, and usually 0.05 μm or more. If the average pore size exceeds the above range, short circuit is likely to occur. In addition, if it is less than the above range, the membrane resistance sometimes increases and the rate characteristics decrease.
[0358] On the other hand, as inorganic materials, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate are used, and materials in the form of particles or fibers are used.
[0359] As the form, a non-woven fabric, a woven fabric, a microporous film or other thin film-shaped material is used. In the case of a thin film, it is preferred to use a thin film with a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film shapes, a diaphragm can also be used in which a composite porous layer containing particles of the above-mentioned inorganic substance is formed on the surface of the positive electrode and / or the negative electrode using a resin binder. For example, a porous layer can be formed on both sides of the positive electrode using a fluororesin as a binder and alumina particles with a particle size of 90% less than 1 μm.
[0360] The electrode mixture group may be any one of a layered structure in which the separator is interposed between the positive electrode and the negative electrode, and a structure in which the positive electrode and the negative electrode are wound into a spiral shape with the separator interposed therebetween. The proportion of the volume of the electrode mixture group in the internal volume of the battery (hereinafter referred to as the electrode mixture group occupancy rate) is usually 40% or more, preferably 50% or more, and usually 90% or less, preferably 80% or less.
[0361] If the electrode mixture group occupancy rate is less than the above range, the battery capacity may become smaller. In addition, if it exceeds the above range, the void space is small, the battery temperature rises, the components expand, or the vapor pressure of the liquid component of the electrolyte increases, and the internal pressure rises, which will reduce the various characteristics of the battery such as the charge and discharge repetitive performance and high temperature storage, and the gas release valve that releases the internal pressure to the outside may sometimes work.
[0362] The current collecting structure is not particularly limited, but in order to more effectively improve the charge-discharge characteristics of the high current density caused by the electrolyte, it is preferred to adopt a structure that reduces the resistance of the wiring part or the joint part. In the case of reducing the internal resistance in this way, the effect of using the electrolyte can be particularly well exerted.
[0363] When the electrode mixture group is the above-mentioned laminated structure, it is preferred to use a structure formed by bundling the metal core parts of each electrode mixture layer and welding them to the terminal. When the area of a piece of electrode mixture becomes larger, since the internal resistance becomes larger, it is also preferred to set multiple terminals in the electrode mixture to reduce the resistance. When the electrode mixture group is the above-mentioned winding structure, multiple lead structures can be set in the positive electrode and the negative electrode respectively, and bundled on the terminal, thereby reducing the internal resistance.
[0364] The material of the housing is not particularly limited as long as it is a material that is stable to the electrolyte used. Specifically, metals such as nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminated film (laminated film) of resin and aluminum foil are used. From the perspective of lightweight, it is preferred to use a metal such as aluminum or an aluminum alloy, or a laminated film.
[0365] In the case of using metal, there can be mentioned a case in which metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed package structure; or a case in which the above metals are used to form a riveted structure through a resin gasket. In the case of using the above laminated film, there can be mentioned a case in which a sealed package structure is formed by thermally bonding resin layers to each other. In order to improve the sealing performance, a resin different from the resin used in the laminated film can also be sandwiched between the above resin layers. In particular, in the case of forming a sealed structure by thermally bonding the resin layers through the collector terminal, since the metal is bonded to the resin, it is preferred to use a resin having a polar group or a modified resin into which a polar group is introduced as the sandwiched resin.
[0366] The secondary battery using the above electrolyte solution may be in any shape, such as cylindrical, square, laminated, button, large, etc. The shape and structure of the positive electrode, negative electrode, and separator may be changed according to the shape of each battery.
[0367] The solid-state secondary battery is preferably an all-solid-state secondary battery. The solid-state secondary battery is preferably a lithium-ion battery, and is also preferably a sulfide-based all-solid-state secondary battery.
[0368] The solid-state secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.
[0369] In the above-mentioned solid-state secondary battery, the binder disclosed in the present invention can be used in an electrode layer or in a solid electrolyte layer.
[0370] A mixture for a solid secondary battery (preferably a mixture sheet) comprising the binder of the present disclosure and a solid electrolyte, and a solid electrolyte layer (preferably a solid electrolyte layer sheet) comprising the binder of the present disclosure and a solid electrolyte are also preferred embodiments of the present disclosure.
[0371] The solid electrolyte used in the binder for the solid-state secondary battery can be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, in the case of using a sulfide-based solid electrolyte, there is an advantage of having flexibility.
[0372] As the above-mentioned sulfide-based solid electrolyte, there is no particular limitation, and it can be selected from Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 Si 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4 (x = 0.6 to 0.8), Li 4+y Ge 1-y Ga y S4 (y = 0.2 to 0.3), LiPSCl, LiCl, Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5), etc., or a mixture of any one or more of them.
[0373] The above-mentioned sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is particularly preferred from the aspect of an electrochemical device having a high energy density for use in a solid-state battery using lithium ions as carriers.
[0374] The above-mentioned oxide-based solid electrolyte preferably has the following compounds: containing an oxygen atom (O), having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electronic insulation.
[0375] As a specific compound example, for example, Li xa La ya TiO3 [xa = 0.3 to 0.7, ya = 0.3 to 0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (Mbb is at least one element selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, Sn, xc satisfies 0≤xc≤5, yc satisfies 0≤yc≤1, zc satisfies 0≤zc≤1, nc satisfies 0≤nc≤6), Li xd (Al,Ga) yd (Ti,Ge) zd Si ad P md O nd (where 1≤xd≤3, 0≤yd≤2, 0≤zd≤2, 0≤ad≤2, 1≤md≤7, 3≤nd≤15), Li (3-2xe) M ee xe D ee O(xe represents a number greater than 0 and less than 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms), Li xf Si yf O zf (1≤xf≤5,0 <yf≤3,1≤zf≤10)、Li xg S yg O zg (1≤xg≤3,0 <yg≤2,1≤zg≤10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 、Li3PO (4-3 / 2w) N w (w satisfies w<1), Li with LISICON (lithium superion conductor) type crystal structure 3.5 Zn 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 ,La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ion conductor) type crystal structure 12 , Li 1+xh+yh(Al,Ga) xh (Ti,Ge) 2-xh Si yh P 3-yh O 12 (where 0≤xh≤1, 0≤yh≤1), Li7La3Zr2O with garnet crystal structure 12 (LLZ), etc. In addition, ceramic materials in which LLZ is replaced by elements are also known. For example, LLZ-based ceramic materials in which LLZ is replaced by at least one element of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) can also be cited. In addition, phosphorus compounds containing Li, P, and O are also preferred. For example, lithium phosphate (Li3PO4), LiPON in which part of the oxygen in lithium phosphate is replaced by nitrogen, and LiPOD 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.
[0376] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in solid-state batteries using lithium ions as carriers, and is particularly preferred from the perspective of electrochemical devices having high energy density.
[0377] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. From the perspective of good Li ion conductivity, an oxide having a crystalline structure is particularly preferred. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, etc.), garnet type (Li7La3Zr2O 12 (LLZ) etc. Among them, NASICON type is preferred.
[0378] The volume average particle size of the oxide-based solid electrolyte is not particularly limited, and is preferably 0.01 μm or more, and more preferably 0.03 μm or more. As an upper limit, it is preferably 100 μm or less, and more preferably 50 μm or less. It should be noted that the average particle size of the oxide-based solid electrolyte particles is measured in the following order. The oxide-based solid electrolyte particles are diluted with water (heptane in the case of substances unstable to water) in a 20 ml sample bottle to adjust to a dispersion of 1% by mass. The diluted dispersed sample is irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample, a laser diffraction / scattering particle size distribution measuring device LA-920 (manufactured by HORIBA) is used to obtain data 50 times at a temperature of 25 ° C using a measuring quartz dish to obtain the volume average particle size. Other detailed conditions, etc., are described in JIS Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are prepared for each level, and their average value is adopted.
[0379] The solid-state secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous films such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fiber.
[0380] The solid-state secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the positive electrode, negative electrode, solid electrolyte layer, etc., and specifically, cylindrical, square, button, laminated, etc. may be used.
[0381] The solid-state secondary battery can be manufactured, for example, by sequentially stacking a positive electrode, a solid electrolyte layer, and a negative electrode and pressing the stacked layers.
[0382] Although the embodiments have been described above, it should be understood that various changes in the embodiments and details can be made without departing from the spirit and scope of the claims.
[0383] Example
[0384] Next, the present disclosure will be described in more detail with reference to Examples, but the present disclosure is not limited to these Examples.
[0385] Various physical properties were measured by the following methods.
[0386] Average primary particle size
[0387] The fluororesin aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the orientation diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.
[0388] Average aspect ratio
[0389] The average aspect ratio is determined by observing an aqueous fluororesin dispersion diluted to a solid content concentration of about 1 mass % with a scanning electron microscope (SEM), performing image processing on 200 or more particles randomly selected, and averaging the ratio of the major axis to the minor axis.
[0390] Polymer solid content
[0391] 1 g of the fluororesin aqueous dispersion was dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heated residual component to the mass (1 g) of the aqueous dispersion was expressed as a percentage.
[0392] HFP content
[0393] Fluororesin powder 19 In the F-NMR measurement, the signal derived from the obtained functional group was calculated based on the following formula.
[0394] HFP content (mass %) = (50A / (50A+25B)) × 100
[0395] (A: integrated value of CF3 signal appearing near -65ppm, B: integrated value of CF2 signal appearing near -120ppm)
[0396] The chemical shift value used was a value obtained by setting the peak top of the CF2 signal derived from the polymer main chain to -120 ppm.
[0397] Standard Specific Gravity (SSG)
[0398] The measurement was performed by the water displacement method according to ASTM D 792 using a sample formed according to ASTM D 4895.
[0399] Endothermic peak temperature
[0400] The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve of a fluororesin that has not been heated to 300°C or higher and is heated at a rate of 10°C / min using a differential scanning calorimeter [DSC].
[0401] Number average molecular weight (Mn)
[0402] The heat of crystallization was determined by the method described in the following document by measuring the temperature drop of a fluororesin melted with a differential scanning calorimeter (DSC). The measurement was performed five times, and the average of the three values excluding the maximum and minimum values was used.
[0403] Literature: Suwa, T.; Takehisa, M.; Machi, S., J.Appl.Polym.Sci.vol.17, pp.3253(1973).
[0404] Moisture content
[0405] The mass of about 20 g of fluororesin powder was measured before and after heating at 150° C. for 2 hours, and the mass was calculated according to the following formula: Three samples were taken, the mass was calculated for each sample, and the average was calculated and used.
[0406] Water content (mass %) = [(mass of fluororesin powder before heating (g)) - (mass of fluororesin powder after heating (g))] / (mass of fluororesin powder before heating (g)) × 100
[0407] Average secondary particle size
[0408] The measurement was conducted in accordance with JIS K6891.
[0409] Apparent density
[0410] The measurement was conducted in accordance with JIS K6892.
[0411] RR100 extrusion pressure (extrusion pressure at compression ratio 100)
[0412] Mix 50g of fluororesin powder and 10.25g of hydrocarbon oil (trade name: Isopar E, manufactured by Exxon Mobil) as an extrusion aid in a polyethylene container for 3 minutes. At room temperature (25±2°C), fill the barrel of the extruder with the above mixture, apply a load of 0.47MPa to the piston inserted into the barrel and maintain it for 1 minute. Then, extrude from the hole at a punching speed of 18mm / min. The ratio of the cross-sectional area of the barrel to the cross-sectional area of the hole is 100. In the second half of the extrusion operation, the value obtained by dividing the load (N) when the pressure reaches a balanced state by the cross-sectional area of the barrel is used as the extrusion pressure (MPa).
[0413] Tensile test
[0414] The strip obtained by extruding the paste was dried at 230°C for 30 minutes to remove the lubricant. The dried strip was cut into appropriate lengths and placed in a furnace heated to 300°C. In the furnace, the strip was stretched to 25 times the length of the strip before the tensile test at a stretching rate of 100% / sec. If the strip did not break during stretching, it was evaluated as being able to be stretched at a stretching rate of 100% / sec.
[0415] Fluorinated compound content
[0416] Weigh 1 g of fluororesin powder, add 10 g (12.6 ml) of methanol, and perform ultrasonic treatment for 60 minutes to obtain an extract. The obtained extract is subjected to LC / MS / MS measurement. The fluorinated compounds in the extract are measured using a liquid chromatography-mass spectrometer (Waters, LC-MS ACQUITY UPLC / TQD). The measurement equipment configuration and LC-MS measurement conditions are shown in Table 1. Using an aqueous solution of a fluorinated compound with a known concentration, an aqueous solution with a content of more than 5 levels is prepared, and an LC / MS analysis of the aqueous solution at each content is performed. The relationship between the content and the area of the region relative to the content is plotted to draw a calibration curve. Using the above calibration curve, the area of the LC / MS chromatogram of the fluorinated compound in the extract is converted into the content of the fluorinated compound.
[0417] It should be noted that the lower limit of detection in this measurement method is 10 mass ppb.
[0418] [Table 1]
[0419]
[0420] Synthesis example 1
[0421] A white solid A was obtained by the method described in Synthesis Example 1 of International Publication No. 2021 / 045228.
[0422] Production example 1
[0423] 3580 g of deionized water, 100 g of paraffin wax and 5.4 g of white solid A were placed in a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature regulating jacket, and the autoclave was replaced with nitrogen while being heated to 70°C to remove oxygen. After 0.50 g of HFP was pressed into the autoclave with TFE, TFE was pressed into the autoclave so that the pressure in the system was 0.78 MPaG, and the temperature in the system was maintained at 70°C under stirring. Next, an aqueous solution of 15.4 mg of ammonium persulfate dissolved in 20 g of water was pressed into the autoclave with TFE to start the polymerization reaction. As the polymerization reaction proceeded, the pressure in the system decreased, but TFE was added to maintain the temperature in the system at 70°C and the pressure in the system at 0.78 MPaG.
[0424] At the moment when 430g of TFE is consumed from the start of polymerization, an aqueous solution prepared by dissolving 18.0mg of hydroquinone as a free radical scavenger in 20g of water is pressed into the mixture with TFE. The polymerization is continued thereafter, and the stirring and supply of TFE are stopped when the polymerization amount of TFE reaches 1540g from the start of polymerization, and the gas in the system is immediately released to make it normal pressure, thereby terminating the polymerization reaction. The aqueous dispersion is taken out, and after cooling, paraffin is separated to obtain a PTFE aqueous dispersion. The solid content concentration of the obtained PTFE aqueous dispersion is 29.6% by mass, and the average primary particle size is 246nm. The average aspect ratio is 1.25.
[0425] Example 1
[0426] The PTFE aqueous dispersion obtained in Preparation Example 1 was diluted to a solid content concentration of 13% by mass, stirred in a container with a stirrer to solidify it, and then filtered with water to obtain a wet powder. The obtained wet powder was placed on a stainless steel mesh tray, and the mesh tray was heat-treated in a hot air circulation electric furnace at 180°C. After 18 hours, the mesh tray was taken out and the mesh tray was air-cooled to obtain PTFE powder. Various physical properties of the obtained PTFE powder were measured. The results are shown in Table 2.
[0427] Production example 2
[0428] A PTFE aqueous dispersion was obtained in the same manner as in Preparation Example 1 except that the amount of HFP added was changed to 0.06 g. The solid content concentration of the obtained PTFE aqueous dispersion was 29.2% by mass, the average primary particle size was 274 nm, and the average aspect ratio was 1.40.
[0429] Example 2
[0430] A PTFE powder was obtained in the same manner as in Example 1 except that the heat treatment temperature was changed to 160° C. using the PTFE aqueous dispersion obtained in Production Example 2.
[0431] The various physical properties of the obtained PTFE powder were measured. The results are shown in Table 2.
[0432] Production example 3
[0433] Polymerization was carried out in the same manner as in Preparation Example 1 except that 3480 g of deionized water and 5.25 g of white solid A were added, no HFP was added, 15.0 mg of ammonium persulfate was pressed in to start polymerization, a free radical scavenger was added when 400 g of TFE was consumed, and polymerization was terminated when 1200 g of TFE was added from the start of polymerization.
[0434] The obtained PTFE aqueous dispersion had a solid content concentration of 25.3% by mass and an average primary particle size of 310 nm.
[0435] Comparative Example 1
[0436] A PTFE powder was obtained in the same manner as in Example 1 except that the heat treatment temperature was changed to 210° C. by using the PTFE aqueous dispersion obtained in Production Example 3.
[0437] The various physical properties of the obtained PTFE powder were measured. The results are shown in Table 2.
[0438] <Production of positive electrode mixture sheet>
[0439] Weigh the Li(Ni 0.6 Mn 0.2 Co 0.2 )O2[NMC622] and PTFE powder as a binder are fully cooled in a refrigerator to make the material at 5°C.
[0440] The cooled NMC622 and the binder were placed in a high-speed stirring mixer to disperse the materials (1 minute, 3000 rpm). Then, carbon black [SUPER P-Li] as a conductive additive was weighed and stirred at 30 rpm for 300 seconds using a pressurized kneader heated to 40°C to obtain a mixture. The composition was adjusted to a mass ratio of positive electrode active material: binder: conductive additive = 96:2:2.
[0441] The obtained mixture was put into a calender roll heated to 80°C to obtain a 1-2 cm 2 The sheet was again put into a calender roll heated to 80°C several times to obtain a sheet.
[0442] After that, the thickness and density were adjusted by a roller press to obtain a thickness of about 90 μm and a density of 3.6 g / cm 3 Positive electrode mixture sheet.
[0443] <Electrode Strength Measurement>
[0444] Cut out the above positive electrode mixture sheet and make a 4mm wide strip test piece. Use a tensile tester (AGS-100NX manufactured by Shimadzu Corporation) to measure at 100mm / min. The distance between the chucks is set to 30mm. Displacement is given until fracture, and the maximum stress of the measurement result is used as the strength of each sample. Comparative Example 1 is set to 100 for comparison.
[0445] Using each of the PTFE powders obtained above, positive electrode mixture sheets were prepared by the above-mentioned method and evaluated.
[0446]
Claims
1. A fluororesin used as a binder for an electrochemical device, wherein: The fluororesin contains tetrafluoroethylene units and hexafluoropropylene units, and is capable of stretching.
2. A fluororesin used as a binder for an electrochemical device, wherein: The fluororesin contains tetrafluoroethylene units and hexafluoropropylene units, and the amount of the hexafluoropropylene units is 0.03 mass % or less based on all polymerized units.
3. An electrochemical device binder, which is an electrochemical device binder substantially composed of fluororesin, wherein: The fluororesin contains tetrafluoroethylene units and hexafluoropropylene units, and is capable of stretching.
4. A binder for an electrochemical device, which is a binder for an electrochemical device substantially composed only of a fluororesin, wherein: The fluororesin contains tetrafluoroethylene units and hexafluoropropylene units, and the amount of the hexafluoropropylene units is 0.03 mass % or less based on all polymerized units.
5. The binder for electrochemical devices according to claim 3 or 4, wherein The fluororesin has an endothermic peak temperature of 320° C. or higher.
6. The binder for an electrochemical device according to any one of claims 3 to 5, wherein The amount of the hexafluoropropylene units is 1.0% by mass or less based on the total polymer units.
7. The binder for an electrochemical device according to any one of claims 3 to 6, wherein The fluororesin is modified polytetrafluoroethylene.
8. The binder for an electrochemical device according to any one of claims 3 to 7, wherein The fluororesin is in the form of powder.
9. The binder for an electrochemical device according to any one of claims 3 to 8, wherein The extrusion pressure of the fluororesin at a compression ratio of 100 is 50 MPa or less. 10 . The binder for an electrochemical device according to claim 3 , which is a binder for a battery. 11 . An electrode mixture comprising the fluororesin according to claim 1 or 2 or the binder for an electrochemical device according to any one of claims 3 to 10, and an electrode active material. The electrode mixture according to claim 11 , which is in the form of a sheet. 13 . An electrode comprising the fluororesin according to claim 1 or 2 or the binder for an electrochemical device according to any one of claims 3 to 10, an electrode active material, and a current collector. 14 . A secondary battery comprising the electrode according to claim 13 .
Citation Information
Patent Citations
Aqueous florinated polymer dispersion containing multishelled modified particle and method
JP1989008022B2
Dispersion containing tetrafluoroethylene copolymer particle and its production
JP1999343317A
Binder for electrode material
JP2004031179A
Dry electrode for energy storage device and its manufacturing method
JP2017517862A
Polytetrafluoroethylene aqueous dispersion
WO2021045228A1